Compositions and methods for preparing battery electrodes
By using carbon-silicon copolymerized materials and appropriate adhesives and conductive materials, the problem of lithium-ion battery anode material breaking due to volume changes during circulation is solved, and the stability of the battery structure and the extension of the battery life are achieved.
Patent Information
- Application Number
- JP2024545904
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-01
- Filing Date
- 2023-03-30
- Publication Date
- 2025-04-15
AI Technical Summary
The volume expansion and contraction caused by the insertion and removal of lithium ions during the circulation process of the existing lithium ion battery negative electrode materials, resulting in the breakage of the material, thereby shortening the battery life.
Using carbon-silicon copolymerized materials as the negative electrode living agent, a negative electrode battery coating containing carbon-silicon copolymerized materials is prepared, and a battery structure with low resistance is formed by combining appropriate adhesives and conductive materials.
It effectively maintains the low resistance of silicon material during circulation, and prevents the material from rupturing due to volume changes, extending the service life of lithium-ion batteries.
Smart Images

Figure 2025510481000001 
Figure 2025510481000002 
Figure 2025510481000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 326,474, filed April 1, 2022, entitled "Compositions and Methods for Preparing Battery Electrodes," which is incorporated by reference in its entirety.
[0002] The present disclosure relates generally to lithium-ion battery anodes and their preparation, as well as batteries including such anodes. [Background technology]
[0003] Lithium-ion batteries (LIBs) are widely used in a variety of applications, from handheld electronics to automobiles. They are a type of rechargeable battery in which lithium ions are transferred from the negative electrode to the positive electrode during discharge and from the positive electrode to the negative electrode during charging. The properties of the electrodes can dramatically affect the performance and safety characteristics of LIBs. Traditionally, the positive electrode active material of LIBs consists of mixed metal oxides of lithium, e.g., cobalt, nickel, and manganese, while the negative electrode active materials include carbon-based materials such as mesocarbon microbeads and graphite. Graphite is widely used as the negative electrode active material due to its high specific capacity, low electrochemical potential compared to lithium, and ability to form a stable solid electrolyte interface (SEI). Nevertheless, there is a commercial demand for lithium-ion battery negative electrode materials with higher lithium storage capacity than can be obtained with graphite.
[0004] Silicon (Si) is desirable for LIB anodes because it has a larger lithium storage capacity than graphite and a lower electrochemical potential compared to lithium. It is therefore desirable to place as much silicon as possible in the anode. However, during cycling, conventional silicon materials undergo volume expansion and contraction due to the insertion and removal of lithium ions. These stresses can cause the silicon material to fracture, resulting in shattering of the anode and reduced life of the LIB.
[0005] Therefore, it would be desirable in the art to provide silicon-containing negative electrode materials that maintain low electrical resistance and accommodate silicon expansion without cracking and delaminating the coated electrodes. Additionally, it would be desirable in the art to provide methods for preparing improved LIB negative electrodes that include such negative electrode materials. Summary of the Invention
[0006] The present technology is generally directed to lithium ion battery anodes and methods for preparing the same, as well as batteries including such anodes. Specifically, the present technology is directed to the preparation and use of lithium ion battery anode slurries including an anode active material including a carbon-silicon composite, one or more binder materials, one or more conductive additive materials, and a solvent.
[0007] Accordingly, in one aspect, a slurry for preparing a lithium ion battery negative electrode is provided, the slurry having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, the slurry comprising: About 75 to about 90% by weight, about 3 to about 75 m 2 a negative electrode active material comprising a carbon-silicon composite having a surface area in the range of 1 / g; 5-15% by weight of a binder material; 1 to 10% by weight of a conductive material; All weight percentages are on a dry weight basis and based on the total weight of the slurry after removal of the solvent.
[0008] In some embodiments, the viscosity of the slurry ranges from about 1300 to about 1700 mPa·s at a shear rate of about 167 s−1.
[0009] In some embodiments, the carbon-silicon composite is about 1 m 2 / g~about 400m 2 / g range of surface area.
[0010] In some embodiments, the carbon-silicon composite has a density of about 0.3 g / cm 3 ~Approx. 1.3g / cm 3 The tap density ranges from 0.01 to 0.1.
[0011] In some embodiments, the carbon-silicon composite comprises greater than about 10% silicon by weight, based on the total weight of the carbon-silicon composite. In some embodiments, the carbon-silicon composite comprises in the range of about 20% to about 85% silicon by weight, based on the total weight of the carbon-silicon composite. In some embodiments, the carbon-silicon composite comprises in the range of about 20% to about 55% silicon, or about 30% to about 35% silicon by weight, based on the total weight of the carbon-silicon composite.
[0012] In some embodiments, the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel. In some embodiments, the carbon-silicon composite comprises a carbonized polyimide aerogel. In some embodiments, the carbon-silicon composite comprises a pore structure, the pore structure comprising a fibrillar morphology and an array of pores surrounding elemental silicon.
[0013] In some embodiments, the silicon in the carbon-silicon composite is present in particulate form, with the particles having an average particle size of about 1 μm or less.
[0014] In some embodiments, the carbon-silicon composite has a specific capacity of at least 400 mAh / g, or at least 1000 mAh / g.
[0015] In some embodiments, the negative electrode active material has a particle size D90 value of 40 μm or less. In some embodiments, the negative electrode active material has a particle size D50 in the range of about 5 μm to about 20 μm. In some embodiments, the negative electrode active material has a particle size D10 value of at least 1 μm.
[0016] In some embodiments, the percentage of solids in the slurry is in the range of about 30% to about 35% by weight. In some embodiments, the percentage of solids in the slurry is in the range of about 35% to about 60% by weight. In some embodiments, the percentage of solids in the slurry is in the range of about 45% to about 50% by weight.
[0017] In some embodiments, the conductive material is selected from the group consisting of carbon, carbon black, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
[0018] In some embodiments, the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile copolymer, acrylonitrile butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphospha The binder material is selected from the group consisting of styrene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, lithium polyacrylic acid, ammonia polyacrylic acid, polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, cyanoethyl sucrose, fluorinated polymer, chlorinated polymer, salt of alginic acid, polyvinylidene fluoride, poly(vinylidene fluoride)-hexafluoropropene, and combinations thereof. In some aspects, the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, polyacrylonitrile, polyacrylic acid, lithium polyacrylic acid, ammonia polyacrylic acid, polyvinylidene fluoride, and combinations thereof. In some aspects, the binder material is polyacrylic acid.
[0019] In some embodiments, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, dimethylsulfoxide, acetonitrile, butylene carbonate, propylene carbonate, ethyl bromide, tetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, water, ethanol, isopropanol, methanol, acetone, n-propanol, t-butanol, and combinations thereof. In some embodiments, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, water, and combinations thereof. In some embodiments, the solvent is water.
[0020] In some embodiments, the pH value of the slurry is from about 6 to about 8.
[0021] In another embodiment, a lithium ion battery negative electrode slurry having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, the slurry comprising: (i) Approximately 3~75m 2 % by weight of a negative electrode active material comprising: (i) a carbon-silicon composite having a surface area in the range of 100 / g; and (ii) a carbon active material; 2 to 15 weight percent of a binder material; 0.5 to 10% by weight of a conductive material; a solvent, where all weight percentages are on a dry weight basis and based on the total weight of the slurry, to provide a lithium ion battery negative electrode slurry.
[0022] In some embodiments, the viscosity of the slurry is in the range of about 1300 to about 1700 mPa·s at a shear rate of about 167 s−1.
[0023] In some embodiments, the graphite is 3 to 5 mm. 2 / g and a particle size D50 value of about 12 μm.
[0024] In some embodiments, the negative electrode active material comprises a ratio of about 80% by weight carbon active material to about 20% by weight carbon-silicon composite.
[0025] In some embodiments, the carbon-silicon composite comprises greater than about 10% silicon by weight based on the total weight of the carbon-silicon composite. In some embodiments, the carbon-silicon composite comprises from about 20% to about 85% silicon by weight, or from about 30% to about 55% silicon by weight based on the total weight of the carbon-silicon composite. In some embodiments, the carbon-silicon composite comprises from about 30% to about 35% silicon by weight based on the total weight of the carbon-silicon composite.
[0026] In some embodiments, the silicon in the carbon-silicon composite is present in particulate form, with the particles having an average particle size of about 1 μm or less.
[0027] In some embodiments, the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel. In some embodiments, the carbon-silicon composite comprises a carbonized polyimide aerogel. In some embodiments, the carbon-silicon composite comprises a pore structure, the pore structure comprising a fibrillar morphology and an arrangement of pores surrounding elemental silicon.
[0028] In some embodiments, the carbon-silicon composite has a density of about 0.3 g / cm to about 1.3 g / cm 3 The tap density ranges from 0.01 to 0.1.
[0029] In some embodiments, the carbon-silicon composite has a specific capacity of at least 400 mAh / g.
[0030] In some embodiments, the negative electrode active material has a particle size D90 value of 40 μm or less. In some embodiments, the negative electrode active material has a particle size D50 in the range of about 5 μm to about 20 μm. In some embodiments, the negative electrode active material has a particle size D10 value of at least 1 μm.
[0031] In some embodiments, the percentage of solids in the slurry is in the range of about 30% to about 35% by weight. In some embodiments, the percentage of solids in the slurry is in the range of about 35% to about 60% by weight. In some embodiments, the percentage of solids in the slurry is in the range of about 45% to about 50% by weight.
[0032] In some embodiments, the carbon active material is selected from the group consisting of mesoporous carbon, natural graphite, synthetic graphite, graphite flake, hard carbon, soft carbon, and combinations thereof.
[0033] In some embodiments, the conductive material is selected from the group consisting of carbon, carbon black, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
[0034] In some embodiments, the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile copolymer, acrylonitrile butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, The binder material is selected from the group consisting of polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, lithiated polyacrylic acid, ammonia polyacrylic acid, polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, fluorinated polymer, chlorinated polymer, salt of alginic acid, polyvinylidene fluoride, poly(vinylidene fluoride)-hexafluoropropene, and combinations thereof. In some aspects, the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, polyacrylonitrile, polyacrylic acid, lithiated polyacrylic acid, ammonia polyacrylic acid, polyvinylidene fluoride, and combinations thereof. In some aspects, the binder material is selected from the group consisting of polyacrylic acid, styrene butadiene rubber, and combinations thereof.
[0035] In some embodiments, the binder material is a styrene butadiene rubber and the slurry further comprises a rheology modifier.
[0036] In some embodiments, the rheology modifier is carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, or a combination thereof. In some embodiments, the rheology modifier is carboxymethyl cellulose.
[0037] In some embodiments, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, dimethylsulfoxide, acetonitrile, butylene carbonate, propylene carbonate, ethyl bromide, tetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, water, ethanol, isopropanol, methanol, acetone, n-propanol, t-butanol, and combinations thereof. In some embodiments, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, water, and combinations thereof. In some embodiments, the solvent is water.
[0038] In some embodiments, the pH value of the slurry is from about 6 to about 8.
[0039] In a further aspect, About 75 to about 90% by weight, about 3 to about 75 m 2 a negative electrode active material comprising a carbon-silicon composite having a surface area in the range of 1 / g; about 2 to about 20 weight percent of a binder material; about 0.5 to about 15 weight percent of a conductive material; Negative electrode compositions are provided where all weight percentages are on a dry weight basis and based on the total weight of the composition.
[0040] In some embodiments, the negative electrode active material further comprises graphite.
[0041] In some embodiments, the negative electrode active material comprises a ratio of about 80% by weight carbon active material to about 20% by weight carbon-silicon composite.
[0042] In some embodiments, the carbon-silicon composite comprises in the range of about 20% to about 85% silicon by weight, based on the total weight of the carbon-silicon composite.
[0043] In some embodiments, the silicon in the carbon-silicon composite is present in particulate form, with the particles having an average particle size of about 1 μm or less.
[0044] In some embodiments, the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel. In some embodiments, the carbon-silicon composite comprises a carbonized polyimide aerogel. In some embodiments, the carbon-silicon composite comprises a pore structure, the pore structure comprising a fibrillar morphology and an arrangement of pores surrounding elemental silicon.
[0045] In some embodiments, the carbon-silicon composite has a density of about 0.3 g / cm 3 ~Approx. 1.3g / cm 3 The tap density ranges from 0.01 to 0.1.
[0046] In some embodiments, the carbon-silicon composite has a specific capacity of at least 400 mAh / g.
[0047] In some embodiments, the conductive material is selected from the group consisting of carbon, carbon black, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
[0048] In some embodiments, the binder material is a styrene butadiene rubber and the negative electrode composition further comprises a rheology modifier.
[0049] In some embodiments, the rheology modifier is carboxymethyl cellulose.
[0050] In yet a further aspect, the negative electrode comprises: A negative electrode substrate; a negative electrode layer disposed on the negative electrode substrate, About 75 to about 90% by weight, about 3 to about 75 m 2 a negative electrode active material comprising a carbon-silicon composite having a surface area in the range of 1 / g; about 2 to about 20 weight percent of a binder material; and about 0.5 to about 15 weight percent of a conductive material, All weight percentages are on a dry weight basis and are based on the total weight of the composition provided in a negative electrode for a lithium ion battery.
[0051] In some embodiments, the substrate is a copper film.
[0052] In some embodiments, the negative electrode layer has a thickness of 2.5 to about 7 mg / cm 2 The powder is supported on the substrate at a density of 0.1 to 100 μm.
[0053] In some embodiments, the negative electrode layer is from about 10 μm to about 300 μm thick.
[0054] In some embodiments, the press density of the negative electrode layer is in the range of about 0.3 to about 1.1 g / cm3.
[0055] In some embodiments, the area capacity of the negative electrode layer is 4.5 to 5.5 mAh / cm2.
[0056] In some embodiments, the electrical conductivity of the negative electrode layer is at least about 10 S / cm.
[0057] In yet a further aspect, a lithium ion battery is provided that includes a positive electrode, a negative electrode including a negative electrode substrate and a negative electrode layer disposed on the negative electrode substrate, and a separator interposed between the positive electrode and the negative electrode.
[0058] In yet another aspect, a process for preparing a lithium ion battery negative electrode slurry comprises: providing a negative electrode material, a binder, a conductive material, and a solvent; combining an anode material, a binder, and a conductive material in a solvent, wherein the slurry is a homogenous dispersion having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, and the solids content of the slurry is in the range of about 30 to 60 wt %, based on the total weight of the slurry.
[0059] In some embodiments, the viscosity of the slurry ranges from about 1300 to about 1700 mPa·s at a shear rate of about 167 s−1.
[0060] In some embodiments, the combining comprises: i) dissolving a binder in a portion of a solvent to form a binder solution; ii) adding a conductive material to the binder solution to form a suspension; iii) mixing the suspension for a period of time; iv) adding a carbon-silicon composite; and v) adding at least a portion of the solvent; vi) mixing the slurry until a homogenous dispersion is obtained.
[0061] In some embodiments, the binder is polyacrylic acid.
[0062] In some embodiments, the process further includes providing graphite and a rheology modifier, and combining the graphite and the rheology modifier with the negative electrode material, the binder, and the conductive material in a solvent.
[0063] In some embodiments, the combining comprises: i) dissolving a rheology modifier in a portion of a solvent to form a rheology modifier solution; ii) adding a conductive material to the rheology modifier solution to form a suspension; iii) mixing the suspension for a period of time; iv) adding a carbon-silicon composite to the suspension; and v) mixing the suspension for a period of time; vi) adding at least a portion of the solvent; vii) adding graphite to the suspension; viii) adding at least a portion of the solvent; vix) adding a binder to form a slurry; vx) mixing the slurry until a homogenous dispersion is obtained.
[0064] In some embodiments, the binder is a styrene butadiene rubber.
[0065] In some embodiments, the rheology modifier is carboxymethyl cellulose.
[0066] In yet a further aspect, a process for preparing a lithium ion battery negative electrode is provided, the process comprising coating a slurry as described herein onto a substrate to form a coated substrate, and drying the coated substrate.
[0067] In some embodiments, the process comprises at least about 1.5 g / cm 3 The method further comprises calendering the mixture to achieve a density of 0.01 g / g.
[0068] The present disclosure includes, but is not limited to, the following aspects.
[0069] Aspect 1: A slurry for preparing a lithium ion battery negative electrode, the slurry having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, 75 to 90% by weight, about 3 to about 75 m 2 a negative electrode active material comprising a carbon-silicon composite having a surface area in the range of 1 / g; 5-15% by weight of a binder material; 1 to 10% by weight of a conductive material; a solvent; All weight percentage values are on a dry weight basis and based on the total weight of the slurry after removal of the solvent.
[0070] Aspect 2: The carbon-silicon composite is about 1 m 2 / g~about 400m 2 2. The slurry of embodiment 1 having a surface area in the range of 1 / g.
[0071] Aspect 3: The carbon-silicon composite has a density of about 0.3 g / cm 3 ~Approx. 1.3g / cm 3 3. The slurry of embodiment 1 or 2, having a tap density in the range of
[0072] Aspect 4: The slurry of any one of Aspects 1-3, wherein the carbon-silicon composite comprises greater than about 10 wt.% silicon, based on the total weight of the carbon-silicon composite.
[0073] Aspect 5: The slurry of any one of Aspects 1-4, wherein the carbon-silicon composite comprises in the range of about 20% by weight to about 85% by weight silicon, based on the total weight of the carbon-silicon composite.
[0074] Aspect 6: The slurry of any one of Aspects 1-5, wherein the carbon-silicon composite comprises in the range of about 20 to about 55 weight percent, or about 30 to about 35 weight percent silicon, based on the total weight of the carbon-silicon composite.
[0075] Aspect 7: The slurry of any one of Aspects 1-6, wherein the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel.
[0076] Example 8: The slurry of any one of Examples 1-7, wherein the carbon-silicon composite comprises a carbonized polyimide aerogel.
[0077] Aspect 9: The slurry of any one of aspects 1 to 8, wherein the carbon-silicon composite comprises a pore structure, the pore structure comprising a fibrillar morphology and an arrangement of pores surrounding elemental silicon.
[0078] Aspect 10: The slurry of any one of aspects 1 to 9, wherein the silicon in the carbon-silicon composite is present in particulate form, the particles having an average particle size of about 1 μm or less.
[0079] Example 11. The slurry of any one of Examples 1 to 10, wherein the carbon-silicon composite has a specific capacity of at least 400 mAh / g, or at least 1000 mAh / g.
[0080] Example 12 The slurry of any one of Examples 1 to 11, wherein the negative electrode active material has a particle size D90 value of 40 μm or less.
[0081] Example 13 The slurry of any one of Examples 1 to 12, wherein the negative electrode active material has a particle size D50 in the range of about 5 μm to about 20 μm.
[0082] Example 14. The slurry of any one of Examples 1 to 13, wherein the negative electrode active material has a particle size D10 value of at least 1 μm.
[0083] Aspect 15: The slurry of any one of Aspects 1 to 14, wherein the percentage of solids in the slurry is in the range of about 30% to about 35% by weight.
[0084] Aspect 16: The slurry of any one of Aspects 1 to 15, wherein the percentage of solids in the slurry is in the range of about 35% to about 60% by weight.
[0085] Aspect 17: The slurry of any one of Aspects 1 to 16, wherein the percentage of solids in the slurry is in the range of about 45% to about 50% by weight.
[0086] Aspect 18: The slurry of any one of aspects 1 to 17, wherein the conductive material is selected from the group consisting of carbon, carbon black, carbon fiber, carbon nanofiber, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
[0087] Aspect 19: The binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile copolymer, acrylonitrile butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile. 19. The slurry of any one of aspects 1-18, wherein the polymer is selected from the group consisting of polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, lithiated polyacrylic acid, ammoniated polyacrylic acid, polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, cyanoethylsucrose, fluorinated polymers, chlorinated polymers, salts of alginic acid, polyvinylidene fluoride, poly(vinylidene fluoride)-hexafluoropropene, and combinations thereof.
[0088] Aspect 20: The slurry of any one of aspects 1 to 19, wherein the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, polyacrylonitrile, polyacrylic acid, lithiated polyacrylic acid, ammoniated polyacrylic acid, polyvinylidene fluoride, and combinations thereof.
[0089] Aspect 21: The slurry of any one of Aspects 1 to 20, wherein the binder material is polyacrylic acid.
[0090] Aspect 22: The slurry of any one of aspects 1 to 21, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, dimethyl sulfoxide, acetonitrile, butylene carbonate, propylene carbonate, ethyl bromide, tetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, water, ethanol, isopropanol, methanol, acetone, n-propanol, t-butanol, and combinations thereof.
[0091] Aspect 23: The slurry of any one of aspects 1 to 22, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, water, and combinations thereof.
[0092] Aspect 24: The slurry of any one of aspects 1 to 23, wherein the solvent is water.
[0093] Aspect 25: The slurry of any one of Aspects 1 to 24, wherein the pH value of the slurry is from about 6 to about 8.
[0094] A lithium ion battery negative electrode slurry having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, the slurry comprising: (i) Approximately 3~75m 2 % by weight of a negative electrode active material comprising: (i) a carbon-silicon composite having a surface area in the range of 100 / g; and (ii) a carbon active material; 2 to 15 weight percent of a binder material; 0.5 to 10% by weight of a conductive material; A solvent, All weight percentage values are on a dry weight basis and based on the total weight of the slurry.
[0095] Aspect 27: The graphite is 3 to 5 m 2 27. The slurry of embodiment 26 having a surface area of 1 / g and a particle size D50 value of about 12 μm.
[0096]
[0041] Example 28: The slurry of example 26 or 27, wherein the negative electrode active material comprises a ratio of about 80% by weight of carbon active material to about 20% by weight of carbon-silicon composite.
[0097] Aspect 29: The slurry of any one of aspects 26 to 28, wherein the carbon-silicon composite comprises greater than about 10 weight percent silicon, based on the total weight of the carbon-silicon composite.
[0098] Aspect 30: The slurry of any one of aspects 26-29, wherein the carbon-silicon composite comprises in the range of about 20 to about 85 weight percent, or about 30 to about 55 weight percent, silicon, based on the total weight of the carbon-silicon composite.
[0099] Aspect 31: The slurry of any one of aspects 26 to 30, wherein the carbon-silicon composite comprises in the range of about 30% by weight to about 35% by weight silicon, based on the total weight of the carbon-silicon composite.
[0100] Example 32: The slurry of any one of Examples 26-31, wherein the silicon in the carbon-silicon composite is present in particulate form, the particles having an average particle size of about 1 μm or less.
[0101] Example 33: The slurry of any one of Examples 26 to 32, wherein the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel.
[0102] Example 34: The slurry of any one of Examples 26 to 33, wherein the carbon-silicon composite comprises a carbonized polyimide aerogel.
[0103] Aspect 35: The slurry of any one of aspects 26 to 34, wherein the carbon-silicon composite comprises a pore structure, the pore structure comprising a fibrillar morphology and an arrangement of pores surrounding elemental silicon.
[0104] Aspect 36: The carbon-silicon composite has a mass of about 0.3 g / cm 3 ~Approx. 1.3g / cm3 36. The slurry of any one of embodiments 26 to 35, having a tap density in the range of
[0105] Example 37: The slurry of any one of Examples 26 to 36, wherein the carbon-silicon composite has a specific capacity of at least 400 mAh / g.
[0106] Example 38: The slurry of any one of Examples 26 to 37, wherein the negative electrode active material has a particle size D90 value of 40 μm or less.
[0107] Embodiment 39: The slurry of any one of embodiments 26 to 38, wherein the negative electrode active material has a particle size D50 in the range of about 5 μm to about 20 μm.
[0108] Example 40: The slurry of any one of Examples 26 to 39, wherein the negative electrode active material has a particle size D10 value of at least 1 μm.
[0109] Aspect 41: The slurry of any one of Aspects 26 to 40, wherein the percentage of solids in the slurry is in the range of about 30% to about 35% by weight.
[0110] Embodiment 42: The slurry of any one of embodiments 26 to 41, wherein the percentage of solids in the slurry is in the range of about 35% by weight to about 60% by weight.
[0111] Aspect 43: The slurry of any one of Aspects 26 to 42, wherein the percentage of solids in the slurry is in the range of about 45% to about 50% by weight.
[0112] Aspect 44: The slurry of any one of aspects 26 to 43, wherein the carbon active material is selected from the group consisting of mesoporous carbon, natural graphite, synthetic graphite, graphite flake, hard carbon, soft carbon, and combinations thereof.
[0113] Aspect 45: The slurry of any one of aspects 26 to 44, wherein the conductive material is selected from the group consisting of carbon, carbon black, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
[0114] Aspect 46: The binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile copolymer, acrylonitrile butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polyvinyl alcohol, polyvinyl acetate, polyvinyl chloride, polyvinyl alcohol ... 46. The slurry of any one of embodiments 26 to 45, wherein the polymer is selected from the group consisting of lylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, lithiated polyacrylic acid, ammoniated polyacrylic acid, polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, fluorinated polymer, chlorinated polymer, salt of alginic acid, polyvinylidene fluoride, poly(vinylidene fluoride)-hexafluoropropene, and combinations thereof.
[0115] Aspect 47: A slurry described in any one of aspects 26 to 46, wherein the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, polyacrylonitrile, polyacrylic acid, lithiated polyacrylic acid, ammoniated polyacrylic acid, polyvinylidene fluoride, and combinations thereof.
[0116] Aspect 48: The slurry of any one of aspects 26 to 47, wherein the binder material is selected from the group consisting of polyacrylic acid, styrene butadiene rubber, and combinations thereof.
[0117] Aspect 49: The slurry of any one of aspects 26 to 48, wherein the binder material is styrene butadiene rubber, and the slurry further comprises a rheology modifier.
[0118] Aspect 50: A slurry described in any one of aspects 26 to 49, wherein the rheology modifier is carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, or a combination thereof.
[0119] Aspect 51: The slurry of any one of aspects 26 to 50, wherein the rheology modifier is carboxymethyl cellulose.
[0120] Aspect 52: A slurry according to any one of aspects 26 to 51, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, dimethyl sulfoxide, acetonitrile, butylene carbonate, propylene carbonate, ethyl bromide, tetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, water, ethanol, isopropanol, methanol, acetone, n-propanol, t-butanol, and combinations thereof.
[0121] Aspect 53: The slurry of any one of aspects 26 to 52, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, water, and combinations thereof.
[0122] Aspect 54: The slurry of any one of aspects 26 to 53, wherein the solvent is water.
[0123] Aspect 55: The slurry of any one of aspects 26 to 54, wherein the slurry has a pH value of about 6 to about 8.
[0124] Aspect 56: A slurry according to any one of aspects 1 to 55, wherein the viscosity of the slurry is in the range of about 1300 to about 1700 mPa·s at a shear rate of about 167 s / sec.
[0125] Embodiment 57: A negative electrode composition comprising: About 75 to about 90% by weight, about 3 to about 75 m 2 a negative electrode active material comprising a carbon-silicon composite having a surface area in the range of 1 / g; about 2 to about 20 weight percent of a binder material; About 0.5 to about 15 weight percent of a conductive material. The negative electrode composition, wherein all weight percentages are on a dry weight basis and based on the total weight of the composition.
[0126] Example 58: The negative electrode composition of example 57, wherein the negative electrode active material further comprises graphite.
[0127] Example 59: The negative electrode composition of example 57 or 58, wherein the negative active material comprises a ratio of about 80% by weight of carbon active material to about 20% by weight of carbon-silicon composite.
[0128] Embodiment 60: The negative electrode composition of any one of embodiments 57-59, wherein the carbon-silicon composite comprises in the range of about 20% by weight to about 85% by weight silicon, based on the total weight of the carbon-silicon composite.
[0129] Example 61: The negative electrode composition of any one of Examples 57-60, wherein the silicon in the carbon-silicon composite is present in particulate form, the particles having an average particle size of about 1 μm or less.
[0130] Example 62: The negative electrode composition of any one of Examples 57-61, wherein the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel.
[0131] Example 63: The negative electrode composition of any one of Examples 57-62, wherein the carbon-silicon composite comprises a carbonized polyimide aerogel.
[0132] Aspect 64: The negative electrode composition of any one of aspects 57 to 63, wherein the carbon-silicon composite comprises a pore structure, the pore structure comprising a fibrillar morphology and an arrangement of pores surrounding silicon elements.
[0133] Aspect 65: The carbon-silicon composite has a mass of about 0.3 g / cm 3 ~Approx. 1.3g / cm 3 65. The negative electrode composition of any one of embodiments 57 to 64, having a tap density in the range of
[0134] Example 66: The negative electrode composition of any one of Examples 57-65, wherein the carbon-silicon composite has a specific capacity of at least 400 mAh / g.
[0135] Aspect 67: The negative electrode composition of any one of aspects 57 to 66, wherein the conductive material is selected from the group consisting of carbon, carbon black, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
[0136] Aspect 68: The negative electrode composition of any one of aspects 57 to 67, wherein the binder material is styrene butadiene rubber and the negative electrode composition further comprises a rheology modifier.
[0137] Aspect 69: The negative electrode composition of aspect 68, wherein the rheology modifier is carboxymethyl cellulose.
[0138] Aspect 70. A negative electrode for a lithium ion battery, comprising: A negative electrode substrate; a negative electrode layer disposed on the negative electrode substrate, the negative electrode layer comprising the negative electrode composition of any one of aspects 57 to 69.
[0139] Example 71: The negative electrode of Example 70, wherein the substrate is a copper film.
[0140] Aspect 72. The negative electrode layer has a thickness of 2.5 to about 4.5 mg / cm. 2 72. The negative electrode of embodiment 70 or 71, wherein the negative electrode is supported on the substrate at a density of
[0141] Aspect 73: The negative electrode of any one of aspects 70 to 72, wherein the negative electrode layer is from about 10 μm to about 300 μm thick.
[0142] Aspect 74: The press density of the negative electrode layer is about 0.3 to about 2 g / cm 3 The negative electrode of any one of embodiments 70 to 73, wherein the range is:
[0143] Aspect 75: The area capacity of the negative electrode layer is 4.5 to 5.5 mAh / cm 2 The negative electrode of any one of embodiments 70 to 74, wherein
[0144] Example 76: The negative electrode of any one of Examples 70 to 75, wherein the negative electrode layer has a conductivity of at least about 10 S / cm.
[0145] Aspect 77: A positive electrode and A negative electrode according to any one of aspects 70 to 76; and a separator interposed between the positive electrode and the negative electrode.
[0146] Aspect 78. A process for preparing a lithium ion battery negative electrode slurry, comprising: providing a negative electrode material, a binder, a conductive material, and a solvent; combining the negative electrode material, the binder, and the conductive material in the solvent, wherein the slurry is a homogenous dispersion having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, and a solids content of the slurry is in the range of about 30 to 60 wt %, based on a total weight of the slurry.
[0147] Aspect 79: Combining i) dissolving the binder in a portion of the solvent to form a binder solution; ii) adding the conductive material to the binder solution to form a suspension; iii) mixing the suspension for a period of time; iv) adding said carbon-silicon composite; v) adding at least a portion of the solvent; vi) mixing the slurry until a homogenous dispersion is obtained.
[0148] Aspect 80: The process of aspect 77 or 78, wherein the binder is polyacrylic acid.
[0149] Example 81 The process of any one of Examples 77-79, further comprising providing graphite and a rheology modifier, and combining the graphite and the rheology modifier with the negative electrode material in the solvent, the binder, and the conductive material.
[0150] Aspect 82: Combining i) dissolving the rheology modifier in a portion of the solvent to form a rheology modifier solution; ii) adding the conductive material to a rheology modifier solution to form a suspension; iii) mixing the suspension for a period of time; iv) adding said carbon-silicon composite to said suspension; v) mixing the suspension for a period of time; vi) adding at least a portion of the solvent; vii) adding said graphite to the suspension; viii) adding at least a portion of the solvent; and vix) adding said binder to form said slurry; vx) mixing the slurry until a homogenous dispersion is obtained.
[0151] Aspect 83: The process described in Aspect 82, wherein the binder is styrene butadiene rubber.
[0152] Aspect 84: The process described in aspect 82 or 83, wherein the rheology modifier is carboxymethyl cellulose.
[0153] Aspect 85: The process described in any one of aspects 78 to 84, wherein the viscosity of the slurry is in the range of about 1300 to about 1700 mPa·s at a shear rate of about 167 s / s.
[0154] Example 86: A process for preparing a lithium ion battery negative electrode, the process comprising: coating a slurry as described in any one of Examples 1 to 56 onto a substrate to form a coated substrate; and drying the coated substrate.
[0155] Aspect 87: at least about 1.5 g / cm 3 87. The process of claim 86, further comprising calendering to achieve a density of.
[0156] These and other features, aspects, and advantages of the present disclosure will become apparent upon reading of the following detailed description. The present invention includes any combination of two, three, four, or more of the above-described aspects, as well as any combination of any two, three, four, or more features or elements described in this disclosure, regardless of whether such features or elements are expressly combined in the description of a particular aspect herein. The present disclosure is intended to be read holistically such that any separable features or elements of the disclosed invention are intended to be combinable, in any of its various aspects, unless the context explicitly indicates otherwise. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0157] Before describing some example aspects of the present technology, it should be understood that the technology is not limited to the details of structure or process steps set forth in the following description as the technology is capable of other aspects and of being practiced or carried out in various ways.
[0158] In general, the present technology is directed to lithium ion battery anode slurries, lithium ion battery anodes, and methods for preparing each of them, as well as batteries including such anodes. Each of the materials and methods is further described below.
[0159] definition The following definitions are provided for terms used in this disclosure: This application uses the following terms, which are defined below, unless the context of the text in which the term appears requires a different meaning.
[0160] The articles "a" and "an" are used herein to refer to one or to more than one (i.e. to at least one) of the grammatical object of the article.
[0161] The term "about" used throughout this specification is used to describe and explain small variations. For example, the term "about" can refer to ±10% or less, or ±5% or less, such as ±2% or less, ±1% or less, ±0.5% or less, ±0.2% or less, ±0.1% or less, or ±0.05% or less. All numerical values in this specification are modified by the term "about", whether or not expressly indicated. Values modified by the term "about" naturally include the value explicitly indicated. For example, "about 5.0" must include 5.0.
[0162] In the context of this disclosure, the term "aerogel" or "aerogel material" refers to a gel that includes a framework of interconnected structures, has a corresponding network of interconnected pores integrated within the framework, contains a gas, such as air, as a dispersed interstitial medium, and is characterized by the following physical and structural properties (as determined by nitrogen porosimetry testing) that are attributed to aerogels: (a) an average pore size in the range of about 2 nm to about 100 nm, (b) a porosity of at least 80% or greater, and (c) a porosity of at least about 20 nm as measured by nitrogen adsorption analysis. 2 / g or more, for example, 20 to 100 m 2 / g, or even 100m 2 / g. It can be appreciated that the inclusion of additives such as reinforcing materials or electrochemically active species can reduce the porosity of the resulting aerogel composite. Densification can also reduce the porosity of the resulting aerogel composite.
[0163] In the context of this disclosure, the term "surface area" refers to the total volume occupied by a given weight of a material. The terms "surface area" and "specific surface area" are used synonymously with "BET surface area" and have their ordinary meanings herein referring to the Brunauer, Emmett, Teller method for determining surface area by N2 adsorption.
[0164] Thus, the aerogel materials of the present disclosure include any aerogel or other open-cell compound that meets the defining elements set forth in the previous paragraph, including compounds that can also be classified as xerogels, cryogels, ambigels, microporous materials, and the like.
[0165] As used herein, the terms "xerogel" and "ambigel" refer to gels comprising an open, non-fluid colloidal or polymeric network formed by removing all swelling agents from a corresponding wet gel without taking precautions to avoid substantial volume loss or compaction, such as under ambient pressure drying. In contrast to aerogels, xerogels, such as carbon xerogels, generally comprise a compact structure. Xerogels undergo substantial volume loss during ambient pressure drying and can shrink to a volume of about 0 to about 100 m, as measured by nitrogen adsorption analysis. 2 / g, or about 0 to about 20m 2 / g, compared to aerogels.
[0166] In the context of this disclosure, the term "framework" or "framework structure" refers to a network of interconnected oligomeric, polymeric, or colloidal particles that form the solid structure of a gel or aerogel. The polymers or particles that make up the framework structure typically have a diameter of about 100 angstroms. However, the framework structure of the present disclosure can also include a network of interconnected oligomeric, polymeric, or colloidal particles of all diameter sizes that form the solid structure within a gel or aerogel.
[0167] In the context of this disclosure, the term "fibrillar morphology" refers to the structural morphology of nanoporous carbon (e.g., aerogel) that includes struts, rods, fibers, or filaments. It is noted that this fibrillar morphology can be found in both monolithic and powder forms of nanoporous carbon; in other words, monolithic carbon can have a fibrillar morphology and aerogel powders / particles can have a fibrillar morphology.
[0168] Aerogels and xerogels can be formed from inorganic materials, organic materials, or mixtures thereof. When formed from organic materials such as, for example, phenol, resorcinol-formaldehyde (RF), phloroglucinol-furfuraldehyde (PF), polyacrylonitrile (PAN), polyimide (PI), polyurethane (PU), polyurea (PUA), polyamine (PA), polybutadiene, polydicyclopentadiene, and precursors or polymeric derivatives thereof, the organic aerogels can be carbonized (e.g., by pyrolysis) to form carbon aerogels, which can have different or overlapping properties (e.g., pore volume, pore size distribution, morphology, etc.) depending on the precursor materials and methods used.
[0169] The terms "carbon aerogel" and "carbon xerogel" as used herein refer to porous or highly porous carbon-based materials. Some non-limiting examples of carbon aerogels and xerogels include aerogels such as carbonized xerogels and carbonized polyimide aerogels and xerogels. The term "carbonization" in the context of aerogels and xerogels refers to an organic gel (e.g., polyimide) that has been pyrolyzed to decompose or convert the organic aerogel or xerogel composition to at least substantially pure carbon. As used herein, the terms "pyrolyze" or "pyrolysis" or "carbonization" refer to the heat-induced decomposition or conversion of an organic compound or composition to pure or substantially pure carbon.
[0170] As used herein, the term "electrode" refers to either a "cathode" or an "anode." As used herein, the term "positive electrode" is used interchangeably with positive electrode. Similarly, the term "negative electrode" is used interchangeably with negative electrode.
[0171] In the context of this disclosure, the term "capacity" refers to the amount of specific energy or charge that a battery can store. Capacity is specifically measured as the discharge current that a battery can deliver over time per unit mass. It is typically recorded as ampere-hours or milliampere-hours per gram of total electrode mass, Ah / g or mAh / g. For example, a battery with 1 Ah capacity can deliver 1 ampere of current for 1 hour or 0.5 amperes of current for 2 hours. Thus, 1 ampere-hour (Ah) corresponds to 3,600 coulombs of charge. Similarly, the term "milliampere-hour (mAh)" also refers to the unit of storage capacity of a battery, which is 1 / 1000 of an ampere-hour. The capacity of a battery (and particularly the negative electrode) can be determined by methods known in the art, including, for example, but not limited to, applying a fixed constant current load to a fully charged cell until the cell voltage reaches an end of discharge voltage value, and multiplying the constant current by the time to reach the end of discharge voltage is the discharge capacity, and dividing the discharge capacity by the weight of the electrode material or volume. Within the context of this disclosure, capacity measurements are taken according to this method unless otherwise specified. Unless otherwise specified, capacity is reported at cycle 10 of the battery.
[0172] As used herein, the term "battery cycle life" refers to the number of complete charge / discharge cycles that a battery can perform before the nominal capacity of the battery falls below 80% of the initial rated capacity. Cycle life can be affected by various factors that are not significantly affected over time, such as the mechanical strength of the underlying substrate (e.g., carbon aerogel), the connectivity of silicon particles within the aerogel, and the maintenance of the interconnectivity of the aerogel. It is noted that it is a surprising aspect of certain embodiments of the present invention that these factors remain relatively unchanged over time. Cycle life may be determined by methods known in the art, such as, but not limited to, cycle testing, in which a battery cell is subjected to repeated charge / discharge cycles at a given current rate and operating voltage. Within the context of this disclosure, cycle life measurements are obtained according to this method unless otherwise specified. In certain embodiments of the present disclosure, an energy storage device, such as a battery or an electrode thereof, has a cycle life of about 25 cycles or more, 50 cycles or more, 75 cycles or more, 100 cycles or more, 200 cycles or more, 300 cycles or more, 500 cycles or more, 1000 cycles or more, or within a range of any two of these values.
[0173] As used herein, the term "particle size D50" refers to the cumulative 50% size on a volume basis, which is the particle size at the 50% point of the cumulative curve (i.e., the diameter of the particle within the 50th percentile (median) of the particle's volume), where the cumulative curve is drawn such that the particle size distribution is obtained on a volume basis and the total volume is 100%. Furthermore, with respect to the anode material of the present disclosure, particle size D50 refers to the volume average particle size of the secondary particles formed by mutual aggregation and sintering of the primary particles, and refers to the volume average particle size of the primary particles when the particle is composed only of primary particles. Furthermore, D10 refers to the cumulative 10% size on a volume basis (i.e., the diameter of the particle within the 10th percentile of the particle's volume), and D90 refers to the cumulative 90% size on a volume basis (i.e., the diameter of the particle within the 90th percentile of the particle's volume).
[0174] In the context of this disclosure, the term "density" refers to a measure of the mass per unit volume of a material (e.g., the carbon-silicon composite materials described herein). The term "density" generally refers to the true or skeletal density of a material, the bulk density of a material or composition, or the tap density of a material or composition. Density is typically measured in kg / m 3 or g / cm 3 It is reported as:
[0175] The skeletal density of a material is the ratio of the mass of the material to the volume of the material excluding pores within the material and any void space between the particles of the material. The skeletal density of carbon-silicon composite materials may be determined by methods known in the art, including, but not limited to, helium pycnometry.
[0176] The bulk density of a material is the ratio of the mass of the material to the volume of the material, including any pores in the material and any void spaces between the particles of the material. Bulk density, also called "envelope density", can be determined by methods known in the art, including, but not limited to, Standard Test Method for Dimensions and Density of Preformed Block and Board-Type Thermal Insulation (ASTMC303, ASTM International, West Conshohocken, Pa.); Standard Test Methods for Thickness and Density of Blanket or Batt Thermal Insulations (ASTMC167, ASTM International, West Conshohocken, Pa.); or Determination of the Apparent Density of Preformed Pipe Insulation (ISO18098, International Organization for Standardization, Switzerland). In the context of this disclosure, unless otherwise stated, density measurements are taken according to the ASTMC167 standard.
[0177] In the context of this disclosure, the term "tap density" or "tapped density" of a material is the ratio of the mass of the material to the volume of the material measured when the material is vibrated or tapped under certain conditions. The tap density of a powder represents its random dense packing. Tap density values are higher for more regularly shaped particles (e.g., spheres) compared to irregularly shaped particles. Tap density can be calculated using the formula M / Vf, where M=mass in grams and Vf=tapped volume in cubic centimeters (cm3). Tap density is generally measured by first gently introducing a known sample mass into a graduated cylinder and carefully leveling it without compressing the powder. The cylinder is then mechanically tapped by raising it and allowing it to fall under its own weight using a suitable mechanical tap density tester that provides an appropriate fixed drop distance and nominal drop rate. Standard test methods for tap density measurement are described in MPIF-46, ASTMB-527, and ISO3953.
[0178] Anode slurry In one aspect of the present disclosure, an anode slurry for preparing a lithium ion battery is provided. The slurry includes an anode active material including a carbon-silicon composite. The anode slurry also includes one or more binder materials, one or more conductive materials, and a solvent. The anode slurry may further include a rheology modifier. Each of the slurry components is further described below.
[0179] negative electrode active material Carbon-Silicon Composites The negative electrode slurry disclosed herein comprises a carbon-silicon composite comprising a low bulk density carbon material. In some embodiments, the low bulk density carbon material comprises a skeletal framework comprising carbon nanofibers, and the skeletal framework forms a pore structure comprising an array of interconnected pores surrounding silicon elements. Such materials can be described as having fibrillar morphology. Examples of suitable low bulk density carbon materials, carbon-silicon composites, and processes for making such materials and composites are described, for example, in U.S. Patent Application Publication Nos. 2020 / 0269207 and 2022 / 006929 (both to Zafiropoulos et. al.), as well as U.S. Patent Application Publication Nos. 2022 / 0185985 (to Begag et al.), 2022 / 0278333 (to Zafiropoulos et. al.), 2022 / 0185970 (to Leventis et al.), and 2022 / 0209234 (to Trifu et al.), each of which is incorporated by reference herein with respect to such materials, composites, and processes.
[0180] In some embodiments, the carbon-silicon composite is an aerogel, xerogel, cryogel, or ambigel. In some embodiments, the carbon-silicon composite is an aerogel. In some embodiments, the carbon-silicon aerogel is obtained from carbonization of a suitable organic aerogel. In an exemplary embodiment, the carbon aerogel is formed from a pyrolyzed / carbonized polyimide-based aerogel, i.e., a polymer of polyimide. Even more specifically, the polyimide-based aerogel can be produced using one or more methodologies described in U.S. Pat. Nos. 7,071,287 and 7,074,880 to Rhine et.al., for example, by imidizing a poly(amic) acid and drying the resulting gel using a supercritical fluid. Other suitable methods for making polyimide aerogels (and carbon aerogels derived therefrom) are described, for example, in U.S. Pat. No. 6,399,669 to Suzuki et al.; U.S. Pat. No. 9,745,198 to Leventis et al.; Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261; Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01. doi:10.1557 / opl.2011.90; Chidambareswarapattar et al., One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides and isocyanates and conversion to isomorphic carbons,J.Mater.Chem.,2010,20,9666-9678;Guo et al.,Polyimide Aerogels Cross-Linked through Amine Functionalized Polyoligomeric Silsesquioxane,ACS Appl.Mater.Interfaces 2011,3,546-552;Nguyen et al.,Development of High Temperature,Flexible Polyimide Aerogels,American Chemical Society,proceedings published 2011;Meador et al.,Mechanically Strong,Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine,ACS Appl.Mater.Interfaces,2012,4(2),pp 536-544;Meador et al.,Polyimide Aerogels with Amide Cross-Links:A Low-Cost Alternative for Mechanically Strong Polymer Aerogels,ACS Appl.Mater.Interfaces 2015,7,1240-1249;Pei et al. al.,Preparation and Characterization of Highly Cross-Linked Also contemplated herein are methods for preparing polyimide aerogels, as described in Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups, Langmuir 2014,30,13375-13383. The resulting polyimide aerogels are then pyrolyzed to form polyimide-derived carbon aerogels.
[0181] Silicon can be introduced into the composite in a variety of ways. For example, silicon can be introduced as elemental silicon or in the form of a silicon-containing reagent that is then reduced to silicon. Silicon or a silicon precursor can be introduced into the low bulk density carbon material, such as during or after gelation of an organic (e.g., polyimide) gel prior to carbonization, or into a precursor of the low bulk density carbon material.
[0182] Generally, the silicon is at least partially contained within the pores of the low bulk density carbon material, i.e., the silicon is disposed within the framework of the low density carbon material. As an anode material, the silicon accepts lithium ions during charging and releases lithium ions during discharging. In certain embodiments, the nanoporous carbon network forms an interconnected structure around the silicon, which is connected to the nanoporous carbon at multiple points.
[0183] Silicon is generally present in carbon-silicon composites as silicon particles. In the context of the present disclosure, the term "silicon particles" refers to silicon or silicon-based materials having a range of particle sizes. The particle size of silicon in carbon-silicon composites can vary. Silicon particles of the present disclosure can be nanoparticles, e.g., particles having two or three dimensions ranging from about 1 nm to about 150 nm. Silicon particles of the present disclosure can be fine particles, e.g., micron-sized particles, having a maximum dimension, e.g., the diameter of a substantially spherical particle, ranging from about 150 nm to about 10 micrometers or more. For example, silicon particles of the present disclosure can have a maximum dimension, e.g., the diameter of a substantially spherical particle, of about 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 500 nm, 1 micrometer, 1.5 micrometer, 2 micrometer, 3 micrometer, 5 micrometer, 10 micrometer, 20 micrometer, 40 micrometer, 50 micrometer, 100 micrometer, or a range of any two of these values.
[0184] In some embodiments, silicon particles can be monodisperse or substantially monodisperse. In other embodiments, silicon particles can have a particle size distribution. In the context of this disclosure, the size of silicon particles is provided based on the median of particle size distribution, i.e., D50. In some embodiments, the silicon in the carbon-silicon composite has an average particle size of about 1 μm or less.
[0185] The silicon particles of the present disclosure can be silicon wire, crystalline silicon, amorphous silicon, silicon alloy, silicon oxide (SiOx), coated silicon, e.g., carbon-coated silicon, and any combination thereof. In some embodiments, the silicon particles can be substantially planar flakes, i.e., have a flat fragmented shape, which can also be referred to as a platelet shape. For example, the particle has two substantially flat major surfaces connected by a minor surface that defines a thickness between the major surfaces. In some embodiments, the particle is a flat fragmented shape, e.g., a platelet, having two dimensions, e.g., length and width, of about 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 500 nm, 1 micrometer, 1.5 micrometer, 2 micrometer, 3 micrometer, 5 micrometer, 10 micrometer, 20 micrometer, 40 micrometer, 50 micrometer, 100 micrometer, or a range between any two of these values. In other embodiments, the silicon particles can be substantially spherical, cubic, oblique, elliptical, discoidal, or toroidal.
[0186] The amount of silicon present in the carbon-silicon composite varies depending on the density of the low bulk density carbon material, with lower densities resulting in higher weight percent incorporation of silicon. In some embodiments, the carbon-silicon composite comprises silicon in an amount of about 20% to about 85% by weight, for example, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, or about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or about 85% by weight, based on the total weight of the carbon-silicon composite. In some embodiments, the carbon-silicon composite comprises silicon in an amount of about 30% to about 35% by weight, based on the total weight of the carbon-silicon composite.
[0187] Carbon-silicon composites can be in a variety of different physical forms. In some embodiments, carbon-silicon composites can take the form of a monolith. As used herein, the term "monolith" refers to a material in which the majority (weight) of the low-density skeletal framework contained in the carbon-silicon composite is in the form of a single continuous self-supporting body. With respect to aerogel materials, monolithic aerogel materials include aerogel materials that are initially formed to have a well-defined shape, but may subsequently crack, fracture, or segment into non-self-repeat bodies. For example, irregular chunks may be considered monoliths. Monolithic aerogels can take the form of free-standing structures or reinforced materials with fibers or interpenetrating bubbles.
[0188] In other embodiments, the carbon-silicon composite may be in particulate form, e.g., as beads or as particles, e.g., from grinding a monolithic material. As used herein, the term "beads" is meant to include small discrete units or pieces having a generally spherical shape. In some embodiments, the carbon-silicon composite beads are substantially spherical.
[0189] The carbon-silicon composite in particulate form can have a variety of particle sizes. For spherical particles (e.g., beads), the particle size is the diameter of the particle. For irregular particles, the term "particle size" refers to the largest dimension (e.g., length, width, or height). Particle size can vary depending on the physical form, the method of preparation, and any subsequent physical steps performed. In some embodiments, the carbon-silicon composite in particulate form can have a particle size of about 1 micrometer to about 1 millimeter. For example, a carbon-silicon composite in particulate form can have a particle size of about 1 micrometer, about 2 micrometers, about 3 micrometers, about 4 micrometers, about 5 micrometers, about 6 micrometers, about 7 micrometers, about 8 micrometers, about 9 micrometers, about 10 micrometers, about 15 micrometers, about 20 micrometers, about 25 micrometers, about 30 micrometers, about 35 micrometers, about 40 micrometers, about 45 micrometers, about 50 micrometers, about 60 micrometers, about 70 micrometers, about 80 micrometers, about 90 micrometers, about 100 micrometers, about 200 micrometers, about 300 micrometers, about 400 micrometers, about 500 micrometers, about 600 micrometers, about 700 micrometers, about 800 micrometers, about 900 micrometers, about 1 millimeter, or a range between any two of these values.
[0190] In some embodiments, the carbon-silicon composite has a particle size D90 value of 40 micrometers or less. In some embodiments, the carbon-silicon composite has a particle size D10 value of at least 1 micrometer. In some embodiments, the carbon-silicon composite has a particle size D50 value ranging from about 5 micrometers to about 20 micrometers.
[0191] The density of the carbon-silicon composite can vary. In some embodiments, the carbon-silicon composite has a density of about 0.15 g / cm 3 ~Approx. 1.2g / cm 3 The tap density ranges from 0.01 to 0.1.
[0192] The surface area of the carbon-silicon composite can vary. For example, the surface area can be up to about 100 m 2 / g or 100m 2 In some embodiments, the carbon-silicon composite may have a molecular weight of about 1 m 2 / g~about 400m 2 / g, for example, about 1, about 10, or about 50, about 100, about 200, about 300, or about 400 m 2 In some embodiments, the carbon-silicon composite has a surface area in the range of about 10 m 2 / g~about 100m 2 In some embodiments, the carbon-silicon composite has a surface area in the range of about 10 m 2 / g~about 50m 2 In some embodiments, the carbon-silicon composite has a surface area in the range of about 10 m 2 / g~about 40m 2 In some embodiments, the carbon-silicon composite has a surface area in the range of about 10 m 2 / g ~ approx. 30m 2 In some embodiments, the carbon-silicon composite has a surface area in the range of about 10 m 2 / g~about 20m 2 For example, carbon-silicon composites have surface areas in the range of about 10 m 2 / g, approx. 20m 2 / g, approx. 30m 2 / g, approx. 40m 2 / g, or about 50m 2 In another example, the carbon-silicon composite has a surface area of about 13 m 2 / g surface area.
[0193] The compressive strength of carbon-silicon composites can vary. In the context of this disclosure, the terms "compressive strength", "flexural strength", and "tensile strength" refer to the resistance of a material to failure or cracking under compressive, flexural or bending, and tension or pulling forces, respectively. These strengths are specifically measured as the amount of load / force per unit area resisting the load / force. Typically, they are recorded as pounds per square inch (psi), megapascals (MPa), or gigapascals (GPa). Among other factors, the compressive, flexural, and tensile strengths of a material collectively contribute to the structural integrity of the material, which is useful, for example, to withstand the volume expansion of silicon particles during lithiation in LIBs. With specific reference to Young's modulus, a measure of mechanical strength, the modulus may be determined by methods known in the art, including, for example, but not limited to, Standard Test Practice for Instrumented Indentation Testing (ASTM E2546, ASTM International, West Conshohocken, PA); or Standardized Nanoindentation (ISO 14577, International Organization for Standardization, Switzerland). In the context of this disclosure, unless otherwise stated, Young's modulus measurements are taken in accordance with ASTM E2546 and ISO 14577. In certain embodiments, the carbon-silicon composites of the present disclosure have a Young's modulus of about 0.2 GPa or more, 0.4 GPa or more, 0.6 GPa or more, 1 GPa or more, 2 GPa or more, 4 GPa or more, 6 GPa or more, 8 GPa or more, or a range of any two of these values.
[0194] The capacity of the carbon-silicon composite can vary. In some embodiments, the carbon-silicon composite has a specific capacity of at least about 400 mAh / g. In some embodiments, the carbon-silicon composite has a specific capacity of about 400, about 500, about 600, about 700, about 800, about 900, about 1000, or about 1100 mAh / g. In some embodiments, the carbon-silicon composite has a specific capacity of 1200 mAh / g or more, 1400 mAh / g or more, 1600 mAh / g or more, 1800 mAh / g or more, 2000 mAh / g or more, 2400 mAh / g or more, 2800 mAh / g or more, 3200 mAh / g or more, or a range between any two of these values.
[0195] In some embodiments, the negative electrode material further comprises graphite, such as synthetic graphite, natural graphite, hard carbon, or soft carbon. In some embodiments, the graphite has a molecular weight of 1 to 10 μm. 2 In some embodiments, the graphite has a particle size D50 value of about 12 micrometers. In some embodiments, the graphite has a surface area of 3-5 micrometers. 2 / g and a particle size D50 value of about 12 micrometers.
[0196] The electrical conductivity of the negative electrode material may vary. In the context of this disclosure, the term "electrical conductivity" refers to a measurement of a material's ability to conduct electric current or other things, allowing the flow of electrons through or into it. Electrical conductivity is specifically measured as the electrical conductance / susceptance / admittance of a material per unit size of the material. It is usually recorded as S / m (Siemens / meter) or S / cm (Siemens / centimeter). The electrical conductivity or resistivity of a material may be determined by methods known in the art, including, for example, but not limited to: In-line 4-point resistivity (using the dual configuration test method of ASTMF84-99). Within the context of this disclosure, electrical conductivity measurements are obtained according to the ASTMF84-resistivity (R) measurement, which is obtained by measuring the voltage (V) divided by the current (I), unless otherwise specified. In certain embodiments, the negative electrode materials of the present disclosure have an electrical conductivity of about 10 S / cm or greater, 20 S / cm or greater, 30 S / cm or greater, 40 S / cm or greater, 50 S / cm or greater, 60 S / cm or greater, 70 S / cm or greater, 80 S / cm or greater, or within a range of any two of these values.
[0197] The amount of negative electrode active material present in the slurry may vary depending on the desired slurry properties (e.g., density, viscosity, etc.). In some embodiments, the slurry comprises, on a dry weight basis, about 70 to about 95%, e.g., about 70, about 75, or about 80, about 85, about 90, or about 95% of the negative electrode active material. In some embodiments, the slurry comprises, on a dry weight basis, about 80 to about 95% by weight of the negative electrode active material. In some embodiments, the slurry comprises, on a dry weight basis, about 75 to about 90% by weight of the negative electrode material.
[0198] In certain embodiments, the slurry comprises, on a dry weight basis, a negative electrode active material in an amount of about 75 to about 90 weight percent, the negative electrode material comprising a carbon-silicon composite as described herein.
[0199] In other particular embodiments, the slurry comprises, on a dry weight basis, about 80 to about 95 weight percent of the negative electrode active material, the negative electrode active material comprising the carbon-silicon composite described herein and further comprising a carbon active material, such as mesoporous graphite, synthetic graphite, natural graphite, graphite flake, hard carbon, soft carbon, or a combination thereof. In such embodiments, the relative amounts of the carbon-silicon composite and the carbon active material can vary. For example, the negative electrode active material can include a carbon-silicon composite in an amount of about 1 to about 20 weight percent, e.g., about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10, about 11, about 12, about 13, about 14, about 15, about 16, about 17, about 18, about 19, or about 20 weight percent, based on the total weight of the negative electrode active material, with the remainder of the negative electrode material (e.g., up to about 99 weight percent, or up to about 80 weight percent) being another carbon active material, such as graphite.
[0200] Binder Material The negative electrode slurry includes a binder material. As used herein, the term "binder material" refers to a chemical or substance that provides one or both of cohesion and adhesion. As used herein, cohesion refers to the ability of the binder to hold together the components in the electrode composition. As used herein, adhesion refers to the ability of the binder to hold the components in the electrode composition in place on a current collector, e.g., in a LIB negative electrode. Suitable binder materials generally include polymeric materials. In some embodiments, the binder material may include a rheology modifier as discussed below.
[0201] In some embodiments, the binder material is styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile copolymer, acrylonitrile butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyvinyl alcohol, polyvinyl acetate, polyvinyl chloride ... The binder material may be selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, lithium polyacrylic acid, ammonia polyacrylic acid, polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, fluorinated polymer, chlorinated polymer, salt of alginic acid, polyvinylidene fluoride, poly(vinylidene fluoride)-hexafluoropropene, or combinations thereof. In some embodiments, the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, polyacrylonitrile, polyacrylic acid, lithium polyacrylic acid, ammonia polyacrylic acid, polyvinylidene fluoride, and combinations thereof. In some embodiments, the binder material is polyacrylic acid. In some embodiments, the binder material is styrene butadiene rubber. In some embodiments, the binder material is a mixture of polyacrylic acid and styrene butadiene rubber.
[0202] The molecular weight of the binder material can vary, for example, in some embodiments, the binder material is a polyacrylic acid having an average molecular weight ranging from about 50,000 to about 1,250,000 daltons, or from about 100,000 to about 450,000 daltons.
[0203] The amount of binder material present in the anode slurry can vary. In some embodiments, the amount of binder material in the anode slurry is in the range of about 1% to about 20% by weight, based on the total weight of the slurry, on a dry weight basis, for example, about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10, about 11, about 12, about 13, about 14, about 15, about 16, about 17, about 18, about 19, or about 20% by weight. In some embodiments, the amount of binder material in the anode slurry is in the range of about 2 to about 15% by weight, or about 5 to about 15% by weight, based on the total weight of the slurry, on a dry weight basis. In embodiments including multiple binder materials, it should be understood that the amount of binder per weight reflects the total weight of the binder materials.
[0204] Rheology Modifiers In some embodiments, the negative electrode slurry includes a rheology modifier. As used herein, the term "rheology modifier" refers to a chemical or material that can be used to modify one or more properties of a slurry, such as thickness, viscosity, flowability, pourability, and dispersibility, as well as the leveling, adhesion, and film thickness of a film prepared from such a slurry. Rheology modifiers can be particularly useful in combination with certain binders, such as SBR. Suitable rheology modifiers include, but are not limited to, cellulose derivatives, such as carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, or cyanoethyl cellulose. In some embodiments, the rheology modifier is carboxymethyl cellulose.
[0205] The molecular weight of the rheology modifier can vary, for example, in some embodiments, the rheology modifier is a carboxymethylcellulose having an average molecular weight ranging from about 50,000 to about 600,000 Daltons.
[0206] The amount of rheology modifier present in the negative electrode slurry can vary. In some embodiments, the amount of rheology modifier in the negative electrode slurry is in the range of about 1 wt% to about 5 wt%, for example about 1 wt%, about 2 wt%, or about 3 wt% to about 4 wt%, or about 5 wt%, based on the total weight of the slurry, on a dry weight basis. In some embodiments, the amount of rheology modifier in the negative electrode slurry is in the range of about 1 to about 4 wt%, or about 1 to about 3 wt%, based on the total weight of the slurry, on a dry weight basis.
[0207] Conductive Materials The negative electrode slurry includes a conductive material. As used herein, the term "conductive material" refers to a chemical, substance, or polymeric material that increases the electrical conductivity of an electrode (e.g., a negative electrode or a positive electrode). In some aspects, the conductive material is selected from the group consisting of carbon, carbon black, carbon fiber, carbon nanofiber, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof. In some aspects, the conductive material is carbon black.
[0208] The particle size of the conductive material can vary, hi some embodiments, the particle size of the conductive material is less than about 40 micrometers, for example, from about 1 nanometer to about 40 micrometers, or from about 1 nanometer to about 1 micrometer.
[0209] The amount of conductive material present in the negative electrode slurry can vary. In some embodiments, the negative electrode slurry does not contain a conductive material. In some embodiments, the amount of conductive material in the negative electrode slurry ranges from about 0.1 to 20% by weight on a dry weight basis based on the total weight of the slurry, for example, from about 0.1% by weight, about 0.5% by weight, or from about 1% by weight to about 5% by weight, about 10% by weight, or about 15% by weight, or about 20% by weight on a dry weight basis based on the total weight of the slurry. In some embodiments, the negative electrode slurry includes about 0.5 to about 15% by weight, or about 1 to about 10% by weight of conductive material on a dry weight basis based on the total weight of the slurry.
[0210] solvent The negative electrode slurry includes a solvent. The solvent used in the negative electrode slurry can be any polar organic solvent, water, or a mixture thereof. In some embodiments, the solvent is a polar organic solvent. The polar organic solvent can be any polar protic or polar aprotic organic solvent having a dielectric constant greater than 15, greater than 20, greater than 25, greater than 30, greater than 35, greater than 40, or greater than 45. Non-limiting examples of polar protic organic solvents include alcohols such as benzyl alcohol, ethylene glycol, n-butanol, t-butanol, isopropanol, n-propanol, ethanol, and methanol. Non-limiting examples of polar aprotic organic solvents include ketones, esters, amides, ethers, sulfoxides, nitriles, and carbonates. Non-limiting examples of ketones include methyl propyl ketone, methyl isobutyl ketone, ethyl propyl ketone, diisobutyl ketone, acetophenone, acetone, and the like. Non-limiting examples of esters include ethyl acetate, butyl acetate, isobutyl acetate, n-butyl propionate, and n-pentyl propionate. Non-limiting examples of ethers include tetrahydrofuran, methyl-t-butyl ether, and ethylene glycol monoethyl ether. Non-limiting examples of amides include dimethylformamide and N-methyl-2-pyrrolidone (NMP). Non-limiting examples of carbonates include dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, ethyl methyl carbonate, methyl propyl carbonate, and the like. Other non-limiting examples of polar aprotic organic solvents include acetonitrile, propionitrile, and dimethyl sulfoxide.
[0211] In some embodiments, the solvent comprises water. In some embodiments, the solvent is water. Non-limiting examples of types of water include tap water, distilled water, deionized water, reverse osmosis purified water, or combinations thereof.
[0212] In some embodiments, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, dimethylsulfoxide, acetonitrile, butylene carbonate, propylene carbonate, ethyl bromide, tetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, water, ethanol, isopropanol, methanol, acetone, n-propanol, t-butanol, and combinations thereof. In some embodiments, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, water, and combinations thereof. In some embodiments, the solvent is water.
[0213] The amount of solvent present in the slurry may vary based on, for example, the target viscosity and solids content of the slurry. For example, in some embodiments, the solvent is present in an amount of about 20% to about 80% by weight, about 20% to about 70% by weight, about 20% to about 60% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, about 30% to about 50% by weight, about 30% to about 40% by weight, about 40% to about 70% by weight, about 40% to about 60% by weight, about 40% to about 50% by weight, about 50% to about 80% by weight, about 50% to about 70% by weight, about 50% to about 60% by weight, about 25% to about 60% by weight, about 25% to about 50% by weight, about 25% to about 45% by weight, about 45% to about 60% by weight, about 45% to about 55% by weight, or the like, based on the total weight or volume of the slurry. The compound is present in an amount of about 45% to about 50% by weight, or about 20% to about 80% by volume, about 20% to about 70% by volume, about 20% to about 60% by volume, about 20% to about 50% by volume, about 20% to about 40% by volume, about 30% to 50% by volume, about 30% to about 40% by volume, about 40% to about 70% by volume, about 40% to about 60% by volume, about 40% to about 50% by volume, about 50% to about 80% by volume, about 50% to about 70% by volume, about 50% to about 60% by volume, about 25% to about 60% by volume, about 25% to about 50% by volume, about 25% to about 45% by volume, about 45% to about 60% by volume, about 45% to about 55% by volume, or about 45% to about 50% by volume.
[0214] Preparation of lithium-ion battery anode slurry As a non-limiting illustrative example, the anode slurry described herein is generally prepared by mixing the anode material, binder, and conductive material, each as described herein, in a solvent to achieve uniform dispersion of each of the materials. In some embodiments, a rheology modifier may be utilized. The rheology modifier may be utilized in combination with a particular binder, such as, for example, SBR. The order of addition, mixing time, particular components, and their concentrations may vary based on the conductive material and / or the anode material.
[0215] In some embodiments, the conductive material is graphite and the negative electrode material is a silicon-carbon composite as described herein. In such embodiments, the preparation generally includes preparing a solution of a rheology modifier in a solvent, adding the negative electrode material, adding a conductive material (e.g., graphite), and adding a binder. In some embodiments, the solvent is water.
[0216] In some embodiments, the rheology modifier is carboxymethylcellulose. In some embodiments, the carboxymethylcellulose is dissolved in water to form a solution having a solids content of about 1 to about 4% by weight. In some embodiments, the rheology modifier is a 1.5% by weight aqueous solution of carboxymethylcellulose. The method of preparing the rheology modifier solution can vary based on the particular rheology modifier and batch size. For example, in a large batch, the carboxymethylcellulose and water can be mixed overnight using an overhead mixer. In a small batch, the carboxymethylcellulose and water can be mixed, allowed to sit for a period of time, and mixed again before use. Mixing speeds and times can vary. For example, the mixing speed can be about 1000 to about 3000 rpm, such as about 2000 or about 2500 rpm. The mixing time can be about 5 minutes or about 15 minutes, or about 1 hour, about 12 hours, or about 24 hours.
[0217] Next, at least a portion of the carbon-silicon composite is added along with at least a portion of the total volume of water used in the final slurry. In some embodiments, a portion of the total amount of carbon-silicon composite is added, followed by stirring, and then the remaining portion of the carbon-silicon composite is added. In some embodiments, the portion added first is up to about 50% of the total amount. The total volume of water is based on the BET surface area of the slurry components and the desired solids content (generally 30-60% solids by weight, based on the total weight of the slurry). Slurry components with high surface areas require more water to provide the desired rheological properties of the slurry. In some embodiments, the carbon-silicon composite is present in the slurry in a range of about 10% to about 15% by weight.
[0218] The conductive material (e.g., graphite) is generally added to the rheology modifier solution followed by mixing. The mixing speed and time may vary. For example, the mixing speed may be about 1000 to about 3000 rpm, e.g., about 2000 or about 2500 rpm. Mixing is continued until a homogenous slurry is obtained. In some embodiments, the mixing time may be about 5 minutes to about 30 minutes. In some embodiments, the graphite is added after the carbon-silicon composite. In other embodiments, the graphite is added simultaneously with the carbon-silicon composite. In other embodiments, the carbon-silicon composite is added after the graphite.
[0219] Additional water is added as necessary to provide the required viscosity, as described below, followed by further mixing of the slurry. Mixing speed and time may vary. For example, the mixing speed may be about 1000 to about 3000 rpm, e.g., about 2000 or about 2500 rpm. Mixing is continued until a homogenous slurry is obtained. In some embodiments, the mixing time may be about 5 minutes to about 30 minutes.
[0220] A binder is then added. In some embodiments, the binder is styrene butadiene rubber (SBR). In some embodiments, the SBR is provided as an emulsion having a solids content of less than about 100% by weight, such as less than about 40% by weight. If necessary, additional water is added to provide the required viscosity, followed by further mixing of the slurry. The mixing speed and time may vary. For example, the mixing speed may be about 1000 rpm to about 3000 rpm, such as about 1500 rpm or about 2000 rpm. Mixing is continued until a homogenous slurry is obtained. In some embodiments, the mixing time may be about 30 seconds to about 30 minutes, such as about 1 minute. The speed and time are adjusted to prevent temperature rise due to frictional forces.
[0221] In some embodiments, the conductive material is carbon (e.g., carbon black) and the negative electrode material is a silicon-carbon composite as described herein. In such embodiments, the preparation generally includes preparing a solution of a binder in a solvent, adding a conductive material (e.g., carbon), and adding a negative electrode material. Generally, the binder solution is prepared in a desired solvent. In some embodiments, the binder material is polyacrylic acid. In some embodiments, the solvent is water. In some embodiments, the resulting binder solution has a solids content ranging from about 5% to about 15% by weight. In some embodiments, the binder material is polyacrylic acid and the solution has a solids content of 10% by weight.
[0222] The conductive material (e.g., carbon) is generally added to the binder solution followed by mixing. The mixing speed and time may vary. For example, the mixing speed may be about 1000 to about 3000 rpm, e.g., about 2000 or about 2500 rpm. Mixing is continued until a homogenous slurry is obtained. In some embodiments, the mixing time may be about 5 minutes to about 30 minutes.
[0223] Next, at least a portion of the carbon-silicon composite is added along with at least a portion of the total volume of water used in the final slurry. In some embodiments, a portion of the total amount of carbon-silicon composite is added, followed by stirring, and then the remaining portion of the carbon-silicon composite is added. In some embodiments, the portion added first is up to about 50% of the total amount. The total volume of water is based on the BET surface area of the slurry components and the desired solids content (generally 60-90% solids by weight, based on the total weight of the slurry). Slurry components with high surface areas require more water to provide the desired rheological properties of the slurry. In some embodiments, the carbon-silicon composite is present in the slurry in a range of about 10% to about 15% by weight. If necessary, additional water is added to provide the required viscosity, followed by further mixing of the slurry. Mixing speed and time may vary. For example, the mixing speed may be about 1000 to about 3000 rpm, for example, about 2000 or about 2500 rpm. Mixing is continued until a homogenous slurry is obtained. In some embodiments, the mixing time may be from about 5 minutes to about 30 minutes.
[0224] By any common method, the physical properties of the resulting anode slurry may vary based on the particular components therein and the intended use. For example, the anode slurries may exhibit various pH values, solids contents, viscosities, etc.
[0225] The pH of the negative electrode slurry can vary. In some embodiments, the pH of the negative electrode slurry is about 5 to about 10, for example, about 5 to about 9.5, about 5.5 to about 9, about 5.5 to about 8.5, about 6 to about 8, about 6 to about 7.5, or about 6 to about 7.
[0226] The negative electrode slurry may exhibit various solid contents. As used herein, the term "solid content" refers to the amount of non-volatile material remaining after evaporation of the solvent, and is used synonymously with "percentage of solids." In some embodiments, the percentage of solids in the slurry is in the range of about 30 to about 60% by weight, based on the total weight of the slurry. For example, in some embodiments, the percentage of solids in the slurry is in the range of about 35% to about 60% by weight, about 30% to about 35% by weight, or about 45% to about 50% by weight, based on the total weight of the slurry. In some embodiments, the percentage of solids in the slurry is about 30, about 35, about 40, about 45, about 50, about 55, or about 60% by weight, based on the total weight of the slurry.
[0227] In some embodiments, it is desirable for the anode slurry to be "processable" to facilitate material handling in battery manufacturing. For example, if the anode slurry is too fluid, it may be compositionally unstable (i.e., it may lose homogeneity when exposed to certain forces, such as gravity (e.g., solids settling) or centrifugal forces). If the anode slurry is unstable, solid phase density differences or other attributes may result in separation and / or composition gradients. Alternatively, if the anode slurry is too stiff, the slurry may fracture, crumble, and / or otherwise separate into pieces, which may complicate processing and dimensional control. Formulating the anode slurry within a band of suitable processability can facilitate slurry-based battery manufacturing. The processability of the anode slurry is typically measured by the rheological parameters (e.g., apparent viscosity at a given shear rate (η appr Pa-s), apparent shear rate (γ appr s -1), or effective viscosity). In other words, certain rheological parameter values can define a region within which "processable" formulations can be selected. Specifically, the rheological behavior of the anode slurry can indicate its processability under pressure-driven flow, such as single or twin screw extrusion and / or flow through a die. Rheological parameters can be measured using different types of rheometers, including strain or stress controlled rotational, capillary, slit, extensional, and capillary. In a capillary rheometer, the suspension (e.g., anode slurry) in a reservoir / barrel can flow through a capillary tube / die under pressure generated by a piston. The flow and deformation behavior of the suspension can be characterized by generating flow rate versus pressure drop data by using various capillary dies with different diameters, lengths, and inlet angles.
[0228] Anode slurries can exhibit a wide range of viscosities, which are generally provided in units of millipascal seconds (mPa·s) or centipoise (cP; 1 cP equals 1 mPa·s). In some embodiments, the negative electrode slurry has a viscosity of about 500 mPa·s to about 6,000 mPa·s, e.g., about 500 mPa·s to about 5,500 mPa·s, about 500 mPa·s to about 5,000 mPa·s, about 500 mPa·s to about 4,500 mPa·s, about 500 mPa·s to about 4,000 mPa·s, about 500 mPa·s to about 3,500 mPa·s, about 500 mPa·s to about 3,000 mPa·s, about 1,000 mPa·s to about 6,000 mPa·s, about 1,000 mPa·s to about 5,500 mPa·s, about 1,000 mPa·s to about 5,000 mPa·s, about 1,000 mPa·s to about 4,500 mPa·s, about 1,000mPa s~approx. 4,000mPa s, approx. 1,000mPa s~approx. 3,500mPa s, approx. 1,000mPa s~approx. 3,000mPa ·s, approximately 1,000mPa·s ~ approximately 2,500mPa·s, approximately 1,000mPa·s ~ approximately 2,000mPa·s, approximately 1,500mPa·s ~ approximately 4,00 The viscosity of the composition is from about 0 mPa·s, about 1,500 mPa·s to about 3,500 mPa·s, about 1,500 mPa·s to about 3,000 mPa·s, about 2,000 mPa·s to about 4,000 mPa·s, about 2,000 mPa·s to about 3,500 mPa·s, or about 2,000 mPa·s to about 3,000 mPa·s.
[0229] In some embodiments, the anode slurry has a viscosity of less than 6,000 mPa·s, less than 5,500 mPa·s, less than 5,000 mPa·s, less than 4,500 mPa·s, less than 4,000 mPa·s, less than 3,500 mPa·s, less than 3,000 mPa·s, less than 2,500 mPa·s, less than 2,000 mPa·s, or less than 1,000 mPa·s. In some embodiments, the anode slurry has a viscosity of greater than 1,000 mPa·s, greater than 1,500 mPa·s, greater than 2,000 mPa·s, greater than 2,500 mPa·s, greater than 3,000 mPa·s, greater than 3,500 mPa·s, greater than 4,000 mPa·s, greater than 4,500 mPa·s, greater than 5,000 mPa·s, or greater than 5,500 mPa·s.
[0230] In some aspects, the anode slurries disclosed herein exhibit shear thinning behavior, meaning that the slurries have low viscosity at higher shear rates and high viscosity at lower shear rates. In some aspects, the shear rate experienced by the slurry during application to the substrate (i.e., during drawdown) is in the range of about 100 / s to about 200 / s, for example, on the order of about 167 / s. Exemplary viscosities at various shear rates of formulations according to embodiments disclosed herein are provided in Table 4. In some aspects, the anode slurries have a viscosity in the range of about 1300 to about 1700 mPa·s at a shear rate of about 167 / s. The viscosity at a particular shear rate decreases as the concentration of the carbon-silicon composite in the slurry decreases. Thus, the desired viscosity can be achieved, for example, by adjusting the concentration of the carbon-silicon composite in the slurry to reach the desired viscosity at an appropriate shear rate (e.g., in the range of about 1300 to about 1700 mPa·s at a shear rate of about 167 / sec). See, for example, the viscosity studies disclosed in Example 1 herein. In some embodiments, the anode slurry has a viscosity of about 1300, about 1350, about 1400, about 1450, about 1500, about 1550, about 1600, about 1650, or about 1700 mPa·s at a shear rate of about 167 / sec.
[0231] In some embodiments, the slurry comprises about 5% by weight of the carbon-silicon composite and has a viscosity ranging from about 1100 to about 1700 at a shear rate ranging from about 200 to about 100 / sec. In some embodiments, the slurry comprises about 10% by weight of the carbon-silicon composite and has a viscosity ranging from about 1200 to about 2000 at a shear rate ranging from about 200 to about 100 / sec. In some embodiments, the slurry comprises about 15% by weight of the carbon-silicon composite and has a viscosity ranging from about 1300 to about 2100 at a shear rate ranging from about 200 to about 100 / sec.
[0232] Negative electrode composition In another aspect, a negative electrode composition is provided that includes a negative electrode material as described herein, a binder material as described herein, and a conductive material as described herein. Such compositions can be prepared by removing the solvent from a slurry as described herein by evaporation at ambient or elevated temperature. Such compositions can form a negative electrode layer on a substrate as described further below.
[0233] The amount of negative electrode material (i.e., carbon-silicon composite and optionally graphite) present in the negative electrode composition can vary. In some embodiments, the negative electrode composition comprises a negative electrode material in an amount ranging from about 70 to about 90 weight percent, based on the total weight of the negative electrode composition, on a dry weight basis.
[0234] The amount of binder material present in the negative electrode composition can vary, in some embodiments, the negative electrode composition comprises a binder material in an amount ranging from about 2 to about 30 weight percent, or from about 5 to about 15 weight percent, on a dry weight basis, based on the total dry weight of the negative electrode composition.
[0235] The amount of conductive material present in the negative electrode composition can vary. In some embodiments, the negative electrode composition includes the conductive material in an amount ranging from about 0.5 to about 20 weight percent, on a dry weight basis, based on the total weight of the negative electrode composition.
[0236] Lithium-ion battery negative electrode In another aspect, a lithium ion battery anode is provided that includes a negative electrode layer dispersed on a negative electrode substrate, the negative electrode layer comprising the lithium ion battery anode slurry described herein (i.e., the negative electrode composition described above) disposed on the negative electrode substrate in the form of a dry film.
[0237] By way of non-limiting illustrative example, the lithium ion battery anodes described herein are generally prepared by coating an anode slurry described herein onto a substrate to form a coated substrate and drying the coated substrate to form a lithium ion battery anode. In some aspects, the substrate is coated on one side. In some aspects, the substrate is coated on both sides.
[0238] The material of the substrate and the physical form of the substrate may vary. The negative substrate acts to collect electrons generated by the electrochemical reaction of the battery electrode material or to supply electrons required for the electrochemical reaction. The substrate may be in the form of a foil, sheet, mesh, or film. The thickness of the substrate may vary. In some embodiments, the substrate has a thickness of about 5 μm to about 40 μm before coating. The substrate may be formed of a conductive material such as stainless steel, titanium, nickel, aluminum, copper, or a conductive resin. In some embodiments, the substrate is a copper film.
[0239] In some embodiments, the coating process is carried out using a doctor blade coater, slot die coater, transfer coater, spray coater, roll coater, dip coater, or curtain coater. The term "doctor blade" refers to a process for producing large area films on rigid or flexible substrates. The coating thickness (i.e., of the negative electrode slurry) can be controlled by an adjustable gap width between the coating blade and the coating surface (i.e., the substrate), which allows for the deposition of variable wet layer thicknesses. The term "transfer coating" or "roll coating" refers to a process for producing large area films on rigid or flexible substrates. The slurry is applied onto the substrate by transferring the coating under pressure from the surface of a coating roller. The coating thickness can be controlled by an adjustable gap width between the metering blade and the surface of the coating roller, which allows for the deposition of variable wet layer thicknesses. In a metering roll system, the coating thickness is controlled by adjusting the gap between the metering roller and the coating roller. In some embodiments, the coating process is carried out using a doctor blade with a blade gap height of 60 to 500 micrometers. In some embodiments, the blade height is from about 60 to about 150 micrometers.
[0240] After the negative electrode slurry is coated on the substrate, the coated film disposed on the substrate can be dried in a dryer to obtain a negative electrode. Any dryer capable of drying the coated film can be used. Some non-limiting examples of suitable dryers are batch drying ovens, box drying ovens, hot plates, conveyor drying ovens, multi-zone ovens, and microwave drying ovens. Some non-limiting examples of conveyor drying ovens include conveyor hot air drying ovens, conveyor resistance drying ovens, conveyor induction drying ovens, and conveyor microwave drying ovens.
[0241] After drying the slurry coating, the solvent is removed from the negative electrode slurry layer to provide an initial negative electrode. In some embodiments, the negative electrode is mechanically compressed to densify the negative electrode. Such compression can be performed by calendaring, using plates or rollers for compression. The pressure of the calendaring can vary. In some embodiments, a press density approximately equal to the press density of the negative electrode material is applied. As used herein, the term "press density" refers to the density of the negative electrode after calendaring and refers to the loading (mg / cm) of the negative electrode. 2 ) divided by the thickness (in cm) of the negative electrode coating. Generally, negative electrodes containing negative material in the form of a xerogel have a coating density of about 0.7 to 2 g / cm. 3 while anodes containing anode material in the form of aerogel are compressed to about 0.3-0.7 g / cm 3 is compressed to
[0242] After calendaring, the negative electrode is then dried under vacuum with heating for a period of time. In some embodiments, the negative electrode is dried for a period of about 1 hour to about 24 hours, for example, about 6 hours or about 12 hours. In some embodiments, the temperature is about 50°C, about 80°C, or about 100°C, about 120°C, about 140°C, about 160°C, about 180°C, or about 200°C. In some embodiments, the temperature is about 120°C.
[0243] The amount of negative electrode material (i.e., carbon-silicon composite and optionally graphite) present in the negative electrode layer can vary. In some embodiments, the lithium ion battery negative electrode comprises a negative electrode material in an amount ranging from about 75 to about 85 weight percent, based on the total weight of the negative electrode layer, on a dry weight basis.
[0244] The amount of binder material present in the negative electrode layer can vary. In some embodiments, a lithium ion battery negative electrode layer comprises a binder material in an amount ranging from about 2 to about 20%, or from about 5 to about 15% by weight, based on the total weight of the negative electrode layer, on a dry weight basis.
[0245] The amount of conductive material present in the negative electrode layer can vary. In some embodiments, a lithium ion battery negative electrode layer comprises, on a dry weight basis, an amount of conductive material ranging from about 0.5 to about 15%, based on the total weight of the negative electrode layer.
[0246] The thickness of the negative electrode layer can vary. In some embodiments, the thickness of the negative electrode layer on the substrate is from about 10 μm to about 300 μm, or from about 20 μm to about 100 μm.
[0247] The coating density (i.e., loading) of the negative electrode layer is mg / cm 2 For example, in some embodiments, the coating density is from about 2.5 to about 7 mg / cm 2 In some embodiments, the coating density is about 4 mg / cm 2 In some embodiments, the coating density is about 6.9 mg / cm 2 It is.
[0248] The press density of the negative electrode layer can vary. In some embodiments, the press density is from about 0.3 to about 0.7 g / cm. 3 , or about 0.7 to about 2 g / cm 3 The range is.
[0249] In some embodiments, the negative electrode layer has a capacitance of about 3 to about 8 mAh / cm 2 It has an area capacity of .
[0250] Lithium-ion battery In another aspect, there is provided a lithium ion battery comprising the negative electrode described herein, a positive electrode, and a separator interposed between the positive and negative electrodes.
[0251] All methods described herein may be performed in any suitable order unless otherwise indicated herein or clearly contradicted by context. Any examples provided herein, or the use of exemplary language (e.g., "etc.") are intended merely to better illustrate the materials and methods, and do not impose limitations on their scope unless otherwise claimed. No language in the specification should be construed as indicating any non-claimed element as essential to the practice of the disclosed materials and methods.
[0252] It will be readily apparent to those skilled in the relevant art that suitable modifications and adaptations can be made to the compositions, methods, and applications described herein without departing from the scope of any embodiment. The compositions and methods provided are exemplary and are not intended to limit the scope of the claimed embodiments. All of the various embodiments and options disclosed herein can be combined in all variations. The scope of the compositions, formulations, methods, and processes described herein includes all actual or potential combinations of the embodiments, options, examples, and preferences herein.
[0253] Although the technology herein has been described with reference to specific embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the technology. It will be apparent to those skilled in the art that various modifications and variations can be made to the method and apparatus of the technology without departing from the spirit and scope of the technology. Thus, the technology is intended to cover modifications and variations that come within the scope of the appended claims and their equivalents.
[0254] Throughout this specification, reference to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" means that a particular feature, structure, material, or characteristic described in connection with an embodiment is included in at least one embodiment of the technology. Thus, the appearance of phrases such as "in one or more embodiments," "in a particular embodiment," "in one embodiment," or "in an embodiment" in various places throughout this specification does not necessarily refer to the same embodiment of the technology. Furthermore, particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments. Any ranges cited herein are inclusive.
[0255] All U.S. patent applications, published patent applications, and patents mentioned herein are hereby incorporated by reference.
[0256] Aspects of the present technology are more fully illustrated with reference to the following examples. Before describing some exemplary aspects of the present technology, it should be understood that the present technology is not limited to the details of structure or process steps set forth in the following description. The technology is capable of other aspects and can be practiced or carried out in various ways. The following examples are provided to illustrate certain aspects of the present technology and are not to be construed as limiting thereof.
[0257] Working Example The present invention may be further illustrated by the following non-limiting examples which illustrate the methods.
[0258] Example 1. Preparation of carbon-silicon composite / graphite anode A battery negative electrode comprising carbon-silicon composite and graphite was prepared according to the following general procedure.
[0259] Carboxymethylcellulose powder (CMC; MAC500) was dissolved in water to form a solution with 1.5 wt% solids. For larger batches, the CMC and water were mixed overnight using an overhead mixer. For smaller batches, the CMC and water were mixed at 2500 rpm for 15 minutes, left overnight, and mixed again at 2500 rpm for 5 minutes before use. The solution was added to a Flacktek cup, followed by carbon black (Timcal Super C65; Imersys SA, Paris, France). The slurry was mixed at 2500 rpm for 5 minutes or until a homogenous slurry was produced. Carbon-silicon composite (50% silicon; target density 0.085 g / cm 3 ; prepared according to the method described in Example 11 of U.S. Patent Application Publication No. 2020 / 0269207 by Zafiropoulos et.al.) and graphite (GHDR-14; Imersys SA, Paris, France) were added along with a portion (approximately one-third to two-thirds) of the total volume of water used in the final slurry. The total volume of water is calculated based on the BET surface area of the slurry components and the desired solids content (generally 30-60 wt% solids, based on the total weight of the slurry). Slurry components with high surface areas require more water to provide the desired rheological properties of the slurry. The remaining water was added as needed to provide the required viscosity. An aqueous emulsion of 40 wt% styrene butadiene rubber (SBR; Zeon Chemicals, Louisville, KY) was added to the slurry and mixed at 2000 rpm for approximately 1 minute while avoiding significant frictional heating.
[0260] Using this general method, several slurries were prepared with the ingredients and amounts by weight on a dry weight basis provided in Tables 1, 2, and 3. [Table 1] [Table 2] [Table 3]
[0261] Viscosity testing was performed on each of the slurry formulations in Tables 1, 2, and 3. The viscosities at various shear rates for the three formulations are shown in Table 4. With reference to Table 4, the testing showed that the slurries were shear thinning (i.e., exhibited lower viscosities at higher shear rates and higher viscosities at lower shear rates) and that the lower the amount of active in the blend, the lower the viscosity (in decreasing order: Formulations 2, 1, and 3). The viscosity at a shear rate of 167 is particularly suitable as this approximates the shear rate observed during drawdown as the slurry is being applied to a substrate. [Table 4]
[0262] The prepared slurries were each cast separately onto copper foil using a doctor blade with a blade gap height of 60-150 micrometers. The coated copper foils were dried in air at a temperature of about 80 to about 100 °C on a small scale under ambient conditions or in a zone drying oven. The resulting anodes were calendered to a press density approximately equal to the tap density of the anode material. Generally, anodes containing anode material in the form of a xerogel have a press density of about 0.7 to 1.1 g / cm. 3 The anode containing the aerogel anode material is compressed to about 0.3 to 0.7 g / cm 3 After calendaring, the negative electrode was dried under vacuum at 120° C. for 12 hours.
[0263] Example 2. Preparation of carbon-silicon composite anode A battery negative electrode comprising a carbon-silicon composite was prepared according to the following general procedure.
[0264] Polyacrylic acid (PAA) was dissolved in water to form a solution with 10% solids by weight. The solution was added to a Flacktek cup followed by carbon black (Timcal Super C65). The slurry was mixed at 2500 rpm for 5 minutes or until a homogenous slurry was produced. Carbon-silicon composite (prepared according to the method described in Example 1, Zafiropoulos et.al, US Patent Publication No. 2020 / 0269207, Example 11) was added along with a portion (approximately two-thirds) of the total volume of water used in the final slurry. The remaining water was added as needed to provide the required viscosity, and the slurry was mixed at 2500 rpm for approximately 5 minutes. Using this general method, several slurries were prepared with the ingredients and amounts by weight on a dry weight basis provided in Table 5. [Table 5]
[0265] The resulting slurries were individually cast onto copper foils using a doctor blade with a blade gap height of 60-150 micrometers. The coated copper foils were dried in air at temperatures of about 80 to about 100 °C on a small scale under ambient conditions or in a zone drying oven. The resulting negative electrodes were coated with a 1.6-1.7 g / cm 3 The mixture was calendered and then dried under vacuum at 120° C. for 12 hours.
[0266] Example 3. Preparation of carbon only negative electrode (reference) A battery negative electrode containing only soft carbon was prepared according to the following general procedure.
[0267] Carboxymethylcellulose powder (CMC; MAC500) was dissolved in water to form a solution with 1.5% solids by weight. The solution was added to a Flacktek cup followed by the addition of carbon black (Timcal Super C65). The slurry was mixed at 2500 rpm for 5 minutes or until a homogenous slurry was produced. The soft carbon was added along with the total volume of water used in the final slurry. An aqueous emulsion of styrene butadiene rubber (SBR) was added to the slurry and mixed at 2000 rpm for approximately 1 minute while avoiding significant frictional heating.
[0268] Using this general method, several slurries were prepared with the ingredients and amounts by weight provided in Tables 6, 7, and 8, on a dry weight basis. [Table 6] [Table 7] [Table 8]
[0269] The resulting slurries were individually cast onto copper foils using a doctor blade with a blade gap height of 60 to 150 micrometers. The coated copper foils were dried in air at ambient conditions on a small scale or in a zone drying oven at temperatures of about 80 to about 100 °C. The resulting anodes were calendered to a press density approximately equal to that of soft carbon and subsequently dried at 120 °C under vacuum for 12 hours.
[0270] Example 4. Alternative preparation of carbon-silicon composite / graphite anode A battery negative electrode comprising carbon-silicon composite and graphite was prepared according to the following general procedure.
[0271] Carboxymethylcellulose powder (CMC; MAC500; 1.33 g) was dissolved in water by mixing at 2500 rpm for 15 min to form a solution with 10 wt% solids. The solution was added to a Flacktek cup followed by carbon black (0.1 g; Timcal Super C65; Imersys SA, Paris, France). The slurry was mixed at 2500 rpm for 5 min. Graphite (0.74 g, GHDR-14, Imersys SA, Paris, France) was added and the slurry was mixed at 2500 rpm for 5 min. A portion of the carbon-silicon composite (half the total amount, 0.093 g, 50% silicon, 0.085 g / cm) was added. 3 A target density of 100 mg of styrene butadiene rubber (prepared according to the method described in Example 11 of Zafiropoulos et.al, U.S. Patent Publication No. 2020 / 0269207) was added and the slurry was mixed at 2500 rpm for 5 minutes. The remaining half of the carbon-silicon composite (0.093 g) was added and the slurry was mixed at 2500 rpm for 5 minutes. An aqueous emulsion of 40 wt% styrene butadiene rubber (SBR; Zeon Chemicals, Louisville, KY) was added to a volume of the slurry to obtain 75 mg of SBR and mixed at 2500 rpm for 5 minutes.
[0272] The resulting slurry was mixed at 2 g / cm 3 Press density of 6.9mg / cm 2 The coated foil was cast on copper foil using a doctor blade with a blade gap height of 60-150 micrometers at a loading of 1000 μm. The coated copper foil was dried in air under ambient conditions and subsequently dried under vacuum at 120° C. for 12 hours. The coating thickness was 30 micrometers and the coating mass was 0.82 mg. Compared to the coated foil of Example 1, this alternative procedure provided a more uniform and denser coating layer.
Claims
1. A slurry for preparing a lithium ion battery negative electrode, the slurry having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, the slurry comprising: 75 to 90% by weight of about 3 to about 75 m 2 a negative electrode active material comprising a carbon-silicon composite having a surface area in the range of 100 / g; 5-15% by weight of a binder material; 1 to 10 weight percent of a conductive material; a solvent; All weight percentage values are on a dry weight basis and based on the total weight of the slurry after removal of the solvent.
2. 2. The slurry of claim 1, wherein the viscosity is in the range of about 1300 to about 1700 mPa·s at a shear rate of about 167 sec−1.
3. The carbon-silicon composite is about 1 m 2 / g ~ approx. 400m 2 10. The slurry of claim 1 having a surface area in the range of 100 / g.
4. The carbon-silicon composite has a density of about 0.3 g / cm 3 ~Approx. 1.3g / cm 3 2. The slurry of claim 1 having a tap density in the range of
5. 10. The slurry of claim 1, wherein the carbon-silicon composite comprises greater than about 10% by weight silicon, based on the total weight of the carbon-silicon composite.
6. 10. The slurry of claim 1, wherein the carbon-silicon composite comprises in the range of about 20% to about 85% by weight silicon, based on the total weight of the carbon-silicon composite.
7. 10. The slurry of claim 1, wherein the carbon-silicon composite comprises in the range of about 20 to about 55 wt%, or about 30 to about 35 wt%, silicon based on the total weight of the carbon-silicon composite.
8. 2. The slurry of claim 1, wherein the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel.
9. 2. The slurry of claim 1, wherein the carbon-silicon composite comprises a carbonized polyimide aerogel.
10. 2. The slurry of claim 1, wherein the carbon-silicon composite comprises a pore structure, the pore structure comprising an array of pores surrounding fibrillar morphologies and elemental silicon.
11. 2. The slurry of claim 1, wherein the silicon in the carbon-silicon composite is present in particulate form, the particles having an average particle size of about 1 μm or less.
12. 10. The slurry of claim 1, wherein the carbon-silicon composite has a specific capacity of at least 400 mAh / g, or at least 1000 mAh / g.
13. 10. The slurry of claim 1, wherein the negative electrode active material has a particle size D90 value of 40 μm or less.
14. 10. The slurry of claim 1, wherein the negative electrode active material has a particle size D50 in the range of about 5 μm to about 20 μm.
15. 2. The slurry of claim 1, wherein the negative electrode active material has a particle size D10 value of at least 1 μm.
16. 10. The slurry of claim 1, wherein the percentage of solids in the slurry ranges from about 30% to about 35% by weight.
17. 10. The slurry of claim 1, wherein the percentage of solids in the slurry ranges from about 35% to about 60% by weight.
18. 18. The slurry of claim 17, wherein the percentage of solids in the slurry ranges from about 45% to about 50% by weight.
19. 2. The slurry of claim 1, wherein the conductive material is selected from the group consisting of carbon, carbon black, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
20. The binder material may be styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile copolymer, acrylonitrile butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, 2. The slurry of claim 1, wherein the polymer is selected from the group consisting of polyvinyl chloride, polystyrene, latex, acrylic resins, phenolic resins, epoxy resins, polyesters, polyamides, polyethers, polyimides, polycarboxylates, polycarboxylic acids, polyacrylic acids, lithiated polyacrylic acids, ammoniated polyacrylic acids, polyacrylates, polymethacrylic acids, polymethacrylates, polyacrylamides, polyurethanes, cyanoethylsucrose, fluorinated polymers, chlorinated polymers, salts of alginic acid, polyvinylidene fluoride, poly(vinylidene fluoride)-hexafluoropropene, and combinations thereof.
21. 2. The slurry of claim 1, wherein the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, polyacrylonitrile, polyacrylic acid, lithiated polyacrylic acid, ammoniated polyacrylic acid, polyvinylidene fluoride, and combinations thereof.
22. 10. The slurry of claim 1, wherein the binder material is polyacrylic acid.
23. 2. The slurry of claim 1, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, dimethylsulfoxide, acetonitrile, butylene carbonate, propylene carbonate, ethyl bromide, tetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, water, ethanol, isopropanol, methanol, acetone, n-propanol, t-butanol, and combinations thereof.
24. 2. The slurry of claim 1, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, water, and combinations thereof.
25. The slurry of claim 1 , wherein the solvent is water.
26. 10. The slurry of claim 1, wherein the pH value of the slurry is from about 6 to about 8.
27. A lithium ion battery negative electrode slurry having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, the slurry comprising: (i) Approximately 3 to approximately 75m 2 % of a negative electrode active material, the negative electrode active material comprising: (i) a carbon-silicon composite having a surface area in the range of 100 / g; and (ii) a carbon active material; 2-15% by weight of a binder material; 0.5 to 10 weight percent of a conductive material; a solvent; All weight percentage values are on a dry weight basis and based on the total weight of the slurry.
28. 28. The slurry of claim 27, wherein the viscosity is in the range of about 1300 to about 1700 mPa·s at a shear rate of about 167 sec−1.
29. The graphite is 3 to 5 m 2 30. The slurry of claim 27 having a surface area of 1.0 μm / g and a particle size D50 value of about 12 μm.
30. 28. The slurry of claim 27, wherein the negative electrode active material comprises a ratio of about 80% by weight carbon active material to about 20% by weight carbon-silicon composite.
31. 28. The slurry of claim 27, wherein the carbon-silicon composite comprises greater than about 10 wt.% silicon, based on the total weight of the carbon-silicon composite.
32. 28. The slurry of claim 27, wherein the carbon-silicon composite comprises in the range of about 20% to about 85% by weight, or about 30% to about 55% by weight, silicon based on the total weight of the carbon-silicon composite.
33. 28. The slurry of claim 27, wherein the carbon-silicon composite comprises in the range of about 30% to about 35% by weight silicon, based on the total weight of the carbon-silicon composite.
34. 28. The slurry of claim 27, wherein the silicon in the carbon-silicon composite is present in particulate form, the particles having an average particle size of about 1 μm or less.
35. 28. The slurry of claim 27, wherein the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel.
36. 28. The slurry of claim 27, wherein the carbon-silicon composite comprises a carbonized polyimide aerogel.
37. 28. The slurry of claim 27, wherein the carbon-silicon composite comprises a pore structure, the pore structure comprising an array of pores surrounding fibrillar morphologies and elemental silicon.
38. The carbon-silicon composite has a density of about 0.3 g / cm 3 ~Approx. 1.3g / cm 3 28. The slurry of claim 27 having a tap density in the range of
39. 28. The slurry of claim 27, wherein the carbon-silicon composite has a specific capacity of at least 400 mAh / g.
40. 27. The slurry of claim 26, wherein the negative electrode active material has a particle size D90 value of 40 μm or less.
41. 28. The slurry of claim 27, wherein the negative electrode active material has a particle size D50 in the range of about 5 μm to about 20 μm.
42. 28. The slurry of claim 27, wherein the negative electrode active material has a particle size D10 value of at least 1 μm.
43. 28. The slurry of claim 27, wherein the percentage of solids in the slurry ranges from about 30% to about 35% by weight.
44. 28. The slurry of claim 27, wherein the percentage of solids in the slurry ranges from about 35% to about 60% by weight.
45. 28. The slurry of claim 27, wherein the percentage of solids in the slurry ranges from about 45% to about 50% by weight.
46. 28. The slurry of claim 27, wherein the carbon active material is selected from the group consisting of mesoporous carbon, natural graphite, synthetic graphite, graphite flake, hard carbon, soft carbon, and combinations thereof.
47. 28. The slurry of claim 27, wherein the conductive material is selected from the group consisting of carbon, carbon black, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
48. The binder material may be styrene butadiene rubber, acrylated styrene butadiene rubber, acrylonitrile copolymer, acrylonitrile butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, poly 28. The slurry of claim 27, wherein the polymer is selected from the group consisting of acrylonitrile, polystyrene, latex, acrylic resins, phenolic resins, epoxy resins, polyesters, polyamides, polyethers, polyimides, polycarboxylates, polycarboxylic acids, polyacrylic acids, lithiated polyacrylic acids, ammoniated polyacrylic acids, polyacrylates, polymethacrylic acids, polymethacrylates, polyacrylamides, polyurethanes, fluorinated polymers, chlorinated polymers, salts of alginic acid, polyvinylidene fluoride, poly(vinylidene fluoride)-hexafluoropropene, and combinations thereof.
49. 28. The slurry of claim 27, wherein the binder material is selected from the group consisting of styrene butadiene rubber, acrylated styrene butadiene rubber, polyacrylonitrile, polyacrylic acid, lithiated polyacrylic acid, ammoniated polyacrylic acid, polyvinylidene fluoride, and combinations thereof.
50. 28. The slurry of claim 27, wherein the binder material is selected from the group consisting of polyacrylic acid, styrene butadiene rubber, and combinations thereof.
51. 51. The slurry of claim 50, wherein the binder material is a styrene butadiene rubber and the slurry further comprises a rheology modifier.
52. 52. The slurry of claim 51, wherein the rheology modifier is carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, or a combination thereof.
53. 53. The slurry of claim 52, wherein the rheology modifier is carboxymethyl cellulose.
54. 28. The slurry of claim 27, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, dimethylsulfoxide, acetonitrile, butylene carbonate, propylene carbonate, ethyl bromide, tetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, water, ethanol, isopropanol, methanol, acetone, n-propanol, t-butanol, and combinations thereof.
55. 28. The slurry of claim 27, wherein the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, dimethylformamide, water, and combinations thereof.
56. 28. The slurry of claim 27, wherein the solvent is water.
57. 28. The slurry of claim 27, wherein the pH value of the slurry is from about 6 to about 8.
58. A negative electrode composition comprising: About 75 to about 90% by weight of about 3 to about 75 m 2 a negative electrode active material comprising a carbon-silicon composite having a surface area in the range of 100 / g; about 2 to about 20 weight percent of a binder material; about 0.5 to about 15 weight percent of a conductive material; The negative electrode composition, wherein all weight percentages are on a dry weight basis and based on the total weight of the composition.
59. 60. The negative electrode composition of claim 58, wherein the negative electrode active material further comprises graphite.
60. 60. The negative electrode composition of claim 58, wherein the negative electrode active material comprises a ratio of about 80% by weight carbon active material to about 20% by weight carbon-silicon composite.
61. 60. The negative electrode composition of claim 58, wherein the carbon-silicon composite comprises in the range of about 20% to about 85% by weight silicon, based on the total weight of the carbon-silicon composite.
62. 60. The negative electrode composition of claim 58, wherein the silicon in the carbon-silicon composite is present in particulate form, the particles having an average particle size of about 1 μm or less.
63. 60. The negative electrode composition of claim 58, wherein the carbon-silicon composite is an aerogel, a xerogel, a cryogel, or an ambigel.
64. 60. The negative electrode composition of claim 58, wherein the carbon-silicon composite comprises a carbonized polyimide aerogel.
65. 60. The negative electrode composition of claim 58, wherein the carbon-silicon composite comprises a pore structure, the pore structure comprising a fibrillar morphology and an array of pores surrounding elemental silicon.
66. The carbon-silicon composite has a density of about 0.3 g / cm 3 ~Approx. 1.3g / cm 3 60. The negative electrode composition of claim 58 having a tap density in the range of
67. 60. The negative electrode composition of claim 58, wherein the carbon-silicon composite has a specific capacity of at least 400 mAh / g.
68. 60. The negative electrode composition of claim 58, wherein the conductive material is selected from the group consisting of carbon, carbon black, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, carbon nanotubes, activated carbon, mesoporous carbon graphene, graphene oxide, graphene nanoplatelets, and combinations thereof.
69. 60. The negative electrode composition of claim 58, wherein the binder material is a styrene butadiene rubber and the negative electrode composition further comprises a rheology modifier.
70. 71. The negative electrode composition of claim 70, wherein the rheology modifier is carboxymethyl cellulose.
71. A negative electrode for a lithium ion battery, comprising: A negative electrode substrate; a negative electrode layer disposed on the negative electrode substrate, the negative electrode layer comprising the negative electrode composition of any one of claims 58 to 70.
72. 72. The negative electrode of claim 71 , wherein the substrate is a copper film.
73. The negative electrode layer has a thickness of 2.5 to about 4.5 mg / cm 2 72. The negative electrode of claim 71 , wherein the negative electrode is supported on the substrate at a density of
74. 72. The negative electrode of claim 71, wherein the negative electrode layer is about 10 μm to about 300 μm thick.
75. The press density of the negative electrode layer is about 0.3 to about 1.1 g / cm 3 72. The negative electrode of claim 71, wherein the capacitance is in the range of
76. The area capacity of the negative electrode layer is 4.5 to 5.5 mAh / cm 2 72. The negative electrode of claim 71 ,
77. 72. The negative electrode of claim 71, wherein the negative electrode layer has a conductivity of at least about 10 S / cm.
78. A positive electrode and The negative electrode according to any one of claims 71 to 77, a separator interposed between the positive electrode and the negative electrode.
79. 1. A process for preparing a lithium ion battery negative electrode slurry, comprising: providing a negative electrode material, a binder, a conductive material, and a solvent; combining the negative electrode material, the binder, and the conductive material in the solvent, wherein the slurry is a homogenous dispersion having a viscosity in the range of about 500 mPa·s to about 3500 mPa·s, and a solids content of the slurry is in the range of about 30 to 60 wt %, based on a total weight of the slurry.
80. 80. The process of claim 79, wherein the viscosity is in the range of about 1300 to about 1700 mPa s at a shear rate of about 167 sec-1.
81. Combining i) dissolving the binder in a portion of the solvent to form a binder solution; ii) adding the conductive material to the binder solution to form a suspension; iii) mixing the suspension for a period of time; iv) adding said carbon-silicon composite; v) adding at least a portion of the solvent; vi) mixing the slurry until a homogenous dispersion is obtained.
82. 80. The process of claim 79, wherein the binder is polyacrylic acid.
83. 80. The process of claim 79, further comprising providing graphite and a rheology modifier, and combining the graphite and the rheology modifier with the negative electrode material, the binder, and the conductive material in the solvent.
84. Combining i) dissolving the rheology modifier in a portion of the solvent to form a rheology modifier solution; ii) adding the conductive material to the rheology modifier solution to form a suspension; iii) mixing the suspension for a period of time; iv) adding said carbon-silicon composite to said suspension; v) mixing the suspension for a period of time; vi) adding at least a portion of said solvent; vii) adding said graphite to said suspension; viii) adding at least a portion of said solvent; vix) adding said binder to form said slurry; vx) mixing the slurry until a homogenous dispersion is obtained.
85. 85. The process of claim 84, wherein the binder is a styrene butadiene rubber.
86. 85. The process of claim 84, wherein the rheology modifier is carboxymethyl cellulose.
87. Coating a slurry of any one of claims 1 to 57 onto a substrate to form a coated substrate; and drying the coated substrate.
88. At least about 1.5 g / cm 3 88. The process of claim 87, further comprising calendering to achieve a density of.